Gas absorbing material, its use in gas absorption, gas absorber and gas absorption method, as well as acid gas absorption device, acid gas recovery device, water vapor absorption device, water vapor recovery device, heat exchanger and heat recovery device

The use of polymeric compound particles with amino groups in a gas absorber material addresses the inefficiencies of current acid gas capture technologies by enabling high-speed, energy-efficient absorption and recovery of acid gases.

JP7672002B2Active Publication Date: 2025-05-07JCCL INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023031735
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2014-08-15
Filing Date
2023-03-02
Publication Date
2025-05-07
Estimated Expiration
2035-08-14

AI Technical Summary

Technical Problem

Current technologies for capturing and recovering acid gases, such as carbon dioxide and hydrogen sulfide, from large-scale facilities are energy-intensive and inefficient, particularly in terms of carbon dioxide separation and capture processes.

Method used

A gas absorbing material composed of polymeric compound particles with amino groups, supported on a carrier and stabilized with additives, which enables high-speed gas absorption and dissipation with reduced heat requirements.

Benefits of technology

The gas absorber achieves a large reversible absorption amount per unit volume, allowing for efficient absorption and recovery of acid gases, thereby reducing energy consumption and supporting the goal of a low-carbon society.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007672002000003
    Figure 0007672002000003
  • Figure 0007672002000004
    Figure 0007672002000004
  • Figure 0007672002000005
    Figure 0007672002000005
Patent Text Reader

Abstract

To provide a gas absorbing material and a gas absorber that can realize a gas absorber that has a large reversible absorption amount of gas per unit volume, can absorb and release gas at high speed, and can reduce the amount of heat required for gas release. [Solution] An apparatus for recovering carbon dioxide is provided, which comprises a gas absorption material containing, as a stabilizer, polymer compound particles having an amino group, a polymer compound having at least one of a primary amino group, a secondary amino group, and a tertiary amino group, and a polymer compound produced by polymerizing a polymerizable compound mixed with the polymer compound particles; a gas inlet section for introducing a gas to be treated that contains carbon dioxide into the gas absorption material; a heat supply section for applying heat to the gas absorption material; and a gas outlet section for discharging gas from the gas absorption material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gas absorbing material and a gas absorber capable of reversibly absorbing acidic gases and the like, and to an acidic gas absorption device, an acidic gas recovery device, a water vapor absorption device, a water vapor recovery device, a heat exchanger and a heat recovery device that use the gas absorber. [Background technology]

[0002] In recent years, global warming caused by carbon dioxide and water vapor emitted from large-scale facilities such as thermal power plants, steel mills, and cement plants, and environmental pollution caused by hydrogen sulfide, etc. have become problems. In order to suppress such climate change and environmental pollution and to realize a low-carbon society, research is being conducted on a method of separating and capturing acid gases such as carbon dioxide and hydrogen sulfide, and water vapor emitted from these large-scale facilities, and storing them underground or under the seabed (CCS; Carbon Dioxide Capture and Storage). However, with current technology, the energy costs required for CCS are very high, and a significant reduction in energy costs is required. In particular, since the carbon dioxide separation and capture process accounts for about 60% of the energy costs in CCS, it is essential to increase the efficiency of the carbon dioxide separation and capture process and significantly reduce energy consumption in order to reduce the energy costs in CCS. Additionally, in the field of energy supply, processes are carried out to separate and capture acidic gases such as carbon dioxide and hydrogen sulfide, as well as water vapor, from fuel gases such as natural gas with high concentrations of carbon dioxide, coal gas produced in integrated coal gasification combined cycle (IGCC), and hydrogen used in fuel cells. Improving the efficiency and energy conservation of the carbon dioxide separation and capture process is also important in reducing energy costs in these fields.

[0003] The chemical absorption method using an aqueous amine solution is known as a method for separating carbon dioxide from exhaust gas. In the chemical absorption method, exhaust gas is brought into contact with a low-temperature absorbing solution (aqueous amine solution) in an absorption tower, and carbon dioxide is selectively absorbed into the absorbing solution, which is then transported to a stripping tower and heated to strip the carbon dioxide. This chemical absorption method is actually applied to the treatment of exhaust gas from large-scale facilities. However, the problem is that the absorbing solution needs to be heated to 130°C or higher to strip the carbon dioxide, which requires a large amount of energy. In response to this, Patent Document 1 and Non-Patent Documents 1 and 2 propose the use of a temperature-responsive electrolyte whose basicity changes around a phase transition temperature for separating and recovering carbon dioxide. Patent Document 1 describes an example in which carbon dioxide is absorbed into a temperature-responsive electrolyte at 30°C, and then the temperature-responsive electrolyte is heated to 75°C to release carbon dioxide from the temperature-responsive electrolyte. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2013 / 027668 [Non-patent literature]

[0005] [Non-Patent Document 1] J. Am. Chem. Soc., 134, 18177-, (2012). [Non-Patent Document 2] Angew. Chem, Intl Ed., 53, 2654-, (2014). Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, the temperature-responsive electrolytes described in Patent Document 1 and Non-Patent Documents 1 and 2 can absorb carbon dioxide at 30° C. and dissipate the absorbed carbon dioxide at 75° C., and therefore can greatly reduce the heating temperature during carbon dioxide capture compared to conventional chemical absorption methods. However, when the present inventors investigated this temperature-responsive electrolyte, they found that the reversible absorption amount of acid gas per unit volume was small, and the rates of absorption and dissipation of acid gas were also small, making it insufficient for use in treating exhaust gases and various fuel gases from large-scale facilities.

[0007] In order to solve the problems of the conventional technology, the present inventors have carried out research with the aim of providing a gas absorbing material and a gas absorbent that can realize a gas absorbent having a large reversible absorption amount of gas per unit volume, capable of absorbing and releasing gas at a high speed, and capable of suppressing the amount of heat required for releasing gas to a small amount. In addition, the present inventors have carried out research with the aim of providing an acid gas absorption device and an acid gas recovery device that can efficiently absorb and / or recover acid gas by using the gas absorbent, and further, a water vapor absorption device, a water vapor recovery device, a heat exchanger, and a heat recovery device. [Means for solving the problem]

[0008] As a result of intensive research to solve the above problems, the inventors have found that by using polymer compound particles having amino groups as a gas absorption material, it is possible to realize a gas absorber that has a large reversible absorption amount of gas per unit volume, can absorb and dissipate gas at high speeds, and further requires a small amount of heat for dissipating gas. In particular, it has been found that the absorption and desorption performance of the gas absorbent is further improved by having the following configuration. (1) A gel particle film is supported on a support such as a thin plate, film, or fiber made of a metal, carbon material, or polymer compound. (2) The carriers carrying the gel particle membranes are stacked and accumulated. (3) The gel particle membrane is stabilized and fixed by adding a stabilizer. (4) In order to accelerate the amount and speed of absorption of acidic gases, an absorption promoter is added to the gel particle membrane.

[0009] Specifically, the present invention has the following configuration. [1] A gas absorbing material comprising polymer compound particles having amino groups. [2] The gas absorbing material according to [1], wherein the polymer compound particles are hydrogel particles. [3] The gas absorbing material according to [2], wherein the polymer compound particles have a water content of 0.1 mL or more per 1 g of solid content. [4] The gas absorbing material according to any one of [1] to [3], for absorbing acid gas from a gas containing water vapor and acid gas. [5] The gas absorbing material according to any one of [1] to [4], wherein the polymer compound constituting the polymer compound particles is a polymer of a monomer component containing a monomer having an amino group. [6] The gas absorbing material according to [5], wherein the monomer component contains a substituted acrylamide monomer. [7] The gas absorbing material according to [5] or [6], wherein the monomer having an amino group is an N-(aminoalkyl)acrylamide. [8] The gas absorbing material according to any one of [5] to [7], wherein the monomer having an amino group is a monomer having a tertiary amino group. [9] The gas absorbing material according to any one of [5] to [8], wherein the proportion of the monomer having an amino group in the monomer components is 5 to 95 mol %.

[10] The monomer component includes a monomer having an amino group and a monomer having a hydrophobic group, The gas absorbing material according to any one of [5] to [9], wherein a molar ratio of the monomer having an amino group to the monomer having a hydrophobic group is 5:95 to 95:5.

[11] The gas absorbing material according to

[10] , wherein the monomer having an amino group is an N-(aminoalkyl)acrylamide, and the monomer having a hydrophobic group is an N-alkylacrylamide.

[12] The gas absorbing material according to any one of [1] to

[11] , wherein the polymer compound particles have a polymer density within the particles in a dispersed state after swelling in water of 0.3 to 80%.

[13] The gas absorbing material according to any one of [1] to

[12] , wherein the polymer compound particles have a particle size in a dry state of 5 nm to 10 μm.

[14] The polymer compound particles undergo a phase transition due to a change in temperature, The gas absorbing material according to any one of [1] to

[13] , wherein the polymer compound particles have a phase transition temperature within a range of 10 to 95°C.

[15] The gas absorbing material according to any one of [1] to

[14] , wherein a crosslinked structure is formed between at least some of the polymer compound particles.

[16] The gas absorbing material according to any one of [1] to

[15] , wherein the polymer compound particles have a hydrodynamic particle size of 10 nm to 50 μm after swelling and dispersing in water.

[17] The gas absorbing material according to any one of [1] to

[16] , for absorbing and releasing gas.

[18] The gas absorbing material according to

[17] , for repeating cycles of gas absorption and desorption.

[19] The gas absorbing material according to any one of [1] to

[16] , for absorbing carbon dioxide gas.

[0010]

[20] Use of polymer particles containing amino groups for gas absorption.

[21] The use of polymeric compound particles containing amino groups for the absorption of acid gases from gases containing water vapor and acid gases.

[0011]

[22] A gas absorber comprising a gel particle membrane of a polymer compound having an amino group and a carrier for supporting the gel particle membrane.

[23] The gas absorber according to

[22] , wherein the gel particle membrane contains the gas absorbing material according to any one of [1] to

[19] .

[24] The gas absorber according to

[22] or

[23] , wherein the gel particle membrane is a hydrogel particle membrane containing 10 mass % or more of water based on the total amount of the gel particle membrane.

[25] The carbon dioxide gas emission rate is 0.1 mmol / m 2 / sec or more.

[26] The carbon dioxide gas absorption rate is 0.05 mmol / m 2 / sec or more.

[27] The gas absorber according to any one of

[22] to

[26] , wherein the support is in the form of a thin plate or a cylinder.

[28] The gas absorbent according to any one of

[22] to

[26] , wherein the support is a laminate of a plurality of thin plates.

[29] The gas absorber according to

[27] or

[28] , wherein the thin plate is a metal foil.

[30] The gas absorber according to

[27] or

[28] , wherein the thin plate is made of a carbon material.

[31] The gas absorber according to

[27] or

[28] , wherein the thin plate is a resin film.

[32] The gas absorbent according to any one of

[22] to

[26] , wherein the support is a fiber assembly.

[33] The gas absorbent according to any one of

[22] to

[26] , wherein the carrier is an assembly of a plurality of laminated fiber assemblies.

[34] The gas absorbent according to

[32] or

[33] , wherein the fiber assembly contains inorganic fibers.

[35] The gas absorbent according to

[34] , wherein the inorganic fibers are metal fibers.

[36] The gas absorber according to

[35] , wherein the metal fibers include at least one of stainless steel fibers and aluminum fibers.

[37] The gas absorber according to

[35] , wherein the metal fibers include nickel fibers.

[38] The gas absorber according to any one of

[35] to

[37] , wherein the metal fibers are sintered metal fibers.

[39] The gas absorbent according to

[34] , wherein the inorganic fibers are carbon fibers.

[40] The gas absorbent according to any one of

[32] to

[39] , wherein the fiber assembly contains organic fibers.

[41] The gas absorbent according to

[40] , wherein the fiber assembly is paper.

[42] The gas absorbent according to any one of

[22] to

[26] , wherein the support is a porous body.

[43] The gas absorbent according to

[42] , wherein the porous body is a metal foam.

[44] The carrier has a specific heat at constant pressure of 2500 KJ / (m 3 K) The gas absorbent according to any one of

[22] to

[43] , which is made of the following material:

[45] The gas absorber according to any one of

[22] to

[44] , wherein the support is made of a material having a thermal conductivity of 10 W / (mK) or more.

[46] The gas absorber according to any one of

[22] to

[45] , wherein the surface of the support functions as a heat transfer surface of a heat exchanger.

[47] The gas absorber according to any one of

[22] to

[46] , wherein the support functions as a heat exchanger.

[48] ​​The gas absorber according to any one of

[22] to

[47] , wherein the packing rate of the gel particle membrane is 20% or more.

[49] The gas absorber according to any one of

[22] to

[48] , wherein the gel particle membrane further contains a membrane stabilizer.

[50] The gas absorber according to

[49] , wherein the membrane stabilizer comprises a polymer compound.

[51] The gas absorber according to

[49] , wherein the membrane stabilizer comprises a polymer compound having at least one of a primary amino group, a secondary amino group, and a tertiary amino group.

[52] The gas absorber according to

[51] , wherein the membrane stabilizer comprises polyvinylamine or a derivative of polyvinylamine.

[53] The gas absorber according to any one of

[49] to

[52] , wherein the membrane stabilizer comprises a polymerizable compound.

[54] The gas absorber according to any one of

[49] to

[53] , wherein the membrane stabilizer comprises a polymer compound produced by a polymerization reaction of a polymerizable compound within the gel particle membrane.

[55] The gas absorber according to

[53] or

[54] , wherein the polymerizable compound is acrylamide or an acrylamide derivative.

[56] The gas absorber according to

[55] , containing, as the polymerizable compound, a substituted aminoalkylacrylamide and an acrylamide derivative having two polymerizable groups.

[57] The gas absorber according to any one of

[49] to

[56] , wherein the membrane stabilizer comprises a crosslinking agent.

[58] The gas absorbent according to

[57] , wherein the crosslinking agent is a titanium crosslinking agent.

[59] The gas absorber according to any one of

[49] to

[58] , wherein the content of the membrane stabilizer in the gel particle membrane is 1 to 89 mass % based on the total amount of the gel particle membrane.

[60] The gas absorber according to any one of

[22] to

[59] , wherein the gel particle membrane contains an absorption enhancer.

[61] The gas absorber according to any one of

[22] to

[60] , wherein the gel particle membrane contains an amine-containing compound having a molecular weight of 61 to 10,000.

[62] The gas absorber according to

[61] , wherein the gel particle membrane contains at least one of an amine having an amino group and a hydroxyl group and an amine having three amino groups.

[63] The gel particle membrane is made of isopropylaminoethanol, N,N,N',N'-tetramethyl-1,6-hexanediamine, imino-bis(N,N-dimethylpropylamine) and N,N ’ ,N ” -pentamethyldiethylenetriamine.

[64] The gas absorber according to any one of

[22] to

[63] , wherein the gel particle membrane surface is supported on a heat transfer surface of a heat exchanger.

[65] The gas absorbent according to any one of

[22] to

[64] , wherein the gel particle membrane is capable of reversibly absorbing at least acidic gases.

[66] The gas absorber according to

[65] , wherein the acidic gas is carbon dioxide.

[67] The gas absorber according to

[65] , wherein the acidic gas is hydrogen sulfide.

[68] The gas absorber according to any one of

[22] to

[67] , wherein the gel particle film is capable of reversibly absorbing at least water vapor.

[0012]

[69] A gas absorption method, comprising absorbing a gas into a gel particle membrane of a polymer compound having an amino group.

[70] The gas absorption method according to

[69] , further comprising increasing the temperature of the gel particle film after the gas has been absorbed, thereby dissipating the absorbed gas from the gel particle film.

[71] The gas absorption method according to

[70] , wherein the temperature is increased until a volume phase transition of the polymer compound occurs.

[72] The gas absorption method according to

[70] or

[71] , further comprising lowering the temperature of the gel particle film after dissipating the gas, and allowing the gel particle film to absorb the gas again.

[73] The gas absorption method according to any one of

[70] to

[72] , wherein a cycle consisting of the absorption and the desorption is repeated a plurality of times.

[0013]

[74] An acidic gas absorbing device comprising the gas absorber according to any one of

[22] to

[68] .

[75] An acidic gas recovery apparatus comprising the gas absorber according to any one of

[22] to

[68] .

[76] A water vapor absorbing device comprising the gas absorber according to any one of

[22] to

[68] .

[77] A water vapor recovery device comprising the gas absorbent according to any one of

[22] to

[68] .

[78] A heat exchanger comprising the gas absorber according to any one of

[22] to

[68] .

[79] A heat recovery device comprising the gas absorber according to any one of

[22] to

[68] . Effect of the Invention

[0014] According to the gas absorbing material of the present invention, it is possible to realize a gas absorber that has a large reversible absorption amount of gas per unit volume, can absorb and dissipate gas at a high speed, and can reduce the amount of heat required for dissipating gas. Furthermore, the gas absorber of the present invention has a large reversible absorption amount of gas per unit volume and can absorb and desorb gas at a high speed, and the gel particle membrane is highly stable, so that the initial performance can be reliably maintained even when gas absorption and desorption are repeatedly performed. The acid gas absorption device, acid gas recovery device, water vapor absorption device, water vapor recovery device, heat exchanger, and heat recovery device of the present invention have such gas absorbents, and can efficiently absorb and recover acid gases and water vapor gases, thereby making a significant contribution to the realization of a low-carbon society. [Brief description of the drawings]

[0015] [Figure 1] FIG. 2 is a schematic diagram for explaining the mechanism of phase transition of the polymer compound particles having an amino group used in the present invention and the mechanism of absorption and release of carbon dioxide. [Diagram 2] 1 is a schematic diagram showing a first embodiment of a carbon dioxide gas recovery apparatus to which an acidic gas recovery apparatus of the present invention is applied. [Diagram 3] FIG. 2 is a schematic diagram showing a second embodiment of a carbon dioxide gas recovery apparatus to which the acidic gas recovery apparatus of the present invention is applied. [Figure 4] 1 is a graph showing temperature-dependent particle size change of amine-containing gel particles of Synthesis Example 2. [Diagram 5] 1 is a graph showing the temperature dependence of pH of a particle solution containing amine-containing gel particles of Synthesis Example 2. [Figure 6] 1 is a titration curve of a particle solution containing amine-containing gel particles of Synthesis Example 2 with hydrochloric acid. [Figure 7] 1 is a graph showing the change over time in the amount of carbon dioxide released from the amine-containing gel particles of Synthesis Example 2. [Figure 8]1 is a graph showing the film thickness dependence of the carbon dioxide diffusion rate of a gel particle film and a homogeneous gel film of the amine-containing gel particles (particle size 300 nm) of Synthesis Example 2. [Figure 9] 1 is a graph showing the film thickness dependence of the carbon dioxide diffusion rate of a gel particle film of an amine-containing gel particle (particle size 300 nm) of Synthesis Example 2 and a gel particle film of an amine-containing gel particle (particle size 1 μm) of Synthesis Example 3. [Figure 10] 1 is a graph showing the film thickness dependence of the carbon dioxide absorption rate of the gel particle membrane of the amine-containing gel particle (particle size 300 nm) of Synthesis Example 2, the gel particle membrane of the amine-containing gel particle (particle size 1 μm) of Synthesis Example 3, a gel homogeneous membrane, and the gel particle membrane of the amine-containing gel particle (crosslinked gel particle) of Synthesis Example 4. [Figure 11] FIG. 1 is a schematic diagram showing a reactor for evaluating the gas absorption / desorption performance of a gas absorber. [Figure 12] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particle for a gas absorber having a 0.1 mm or 0.3 mm thick stainless steel thin plate as a carrier and carrying a gel particle film made of amine-containing gel particles. [Figure 13] FIG. 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particle for a gas absorber having a 0.1 mm-thick stainless steel thin plate, iron thin plate, or graphite sheet carrier and carrying a gel particle film made of amine-containing gel particles. [Figure 14] FIG. 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per reactor volume when the thickness of the gel of a gas absorber having a 0.1 mm-thick graphite sheet as a carrier and carrying a gel particle film made of amine-containing gel particles is changed. [Figure 15] FIG. 2 is a schematic diagram, a perspective view (photograph), and a top view (photograph) showing another reactor for evaluating the gas absorption / desorption performance of a gas absorbent. [Figure 16]This is a graph showing the change over time in the amount of carbon dioxide absorbed and released per volume of fiber assembly for various gas absorbents (water addition amounts of 0.4, 0.8, and 1.6 mL, respectively) in which a fiber assembly is used as a carrier and the amount of amine-containing dry gel particles carried is changed to 100, 200, and 400 mg. [Figure 17] This is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particle for various gas absorbents (water addition amounts of 0.4, 0.8, and 1.6 mL, respectively) in which a fiber aggregate is used as a carrier and the amount of amine-containing dry gel particle carried is changed to 100, 200, and 400 mg. [Figure 18] This is a graph showing the change over time in the amount of carbon dioxide absorbed and released per volume of fiber assembly for various gas absorbents having different water contents of 0.4 mL or 0.8 mL in a gel particle film (200 mg of amine-containing dry gel particles supported on a fiber assembly) consisting of amine-containing gel particles supported on a fiber assembly. [Figure 19] FIG. 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particle in various gas absorbers having different water contents of 0.4 mL or 0.8 mL in a gel particle film (200 mg of amine-containing dry gel particles supported) consisting of amine-containing gel particles supported on a fiber assembly. [Figure 20] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per volume of fiber assembly of gas absorbents in which the fiber assembly used as a carrier has fiber diameters of 12 μm and 100 μm. [Figure 21] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles in a gas absorber in which the fiber diameters of the fiber assembly used as a carrier are 12 μm and 100 μm. [Figure 22] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per volume of fiber assembly of gas absorbents in which the fiber assembly used as a carrier has fiber diameters of 8 μm and 12 μm. [Figure 23]1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles in a gas absorber in which the fiber diameters of the fiber assembly used as a carrier are 8 μm and 12 μm. [Figure 24] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles when a gas absorber having a gel particle membrane made of amine-containing gel particles supported on a carrier made of a fiber assembly is placed inside a reaction vessel, and when a gel particle membrane made of the same amount of amine-containing gel particles is placed directly inside the same reaction vessel. [Diagram 25] 1 is a graph showing the relationship between the gel filling rate and the amount of carbon dioxide emitted and absorbed when metal fiber and sintered metal fiber are used. [Figure 26] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles when sintered metal fiber, foam metal, and sintered nickel fiber are used. [Figure 27] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles in a gas absorber carrying a gel particle film made of the amine-containing gel particles of Synthesis Example 1. [Figure 28] 1 is a graph showing the change in vapor pressure with temperature change of a gas absorbent supporting a gel particle film made of amine-containing gel particles of Synthesis Example 1. [Figure 29] 1 is a graph showing the change over time in the amount of carbon dioxide released per mass of amine-containing dry gel particles in a gas absorber in which a polyvinyl alcohol / polyethylene copolymer is added to a gel particle membrane made of amine-containing gel particles. [Diagram 30] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed per mass of amine-containing dry gel particles in a gas absorber in which a polyvinyl alcohol / polyethylene copolymer is added to a gel particle film made of amine-containing gel particles. [Diagram 31] 1 is a photograph showing the change during heat treatment of a film formed from a solution in which a titanium-based crosslinking agent solution was added to a solution of a stabilizer and amine-containing dry gel particles. [Diagram 32]1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles in a gas absorber having a gel particle membrane made of amine-containing gel particles to which a polyvinyl alcohol / polyethylene copolymer and a titanium crosslinking agent have been added. [Diagram 33] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles of a gas absorber obtained by adding a polymerizable compound (DMAPM:BIS=95:5) to a methanol solution of amine-containing gel particles and polymerizing the compound. [Diagram 34] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles of a gas absorber obtained by adding a polymerizable compound (DMAPM:BIS:NIPAM=55:5:45) to a methanol solution of amine-containing gel particles and polymerizing the compound. [Diagram 35] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles of a gas absorber obtained by adding a polymerizable compound (DMAPM:BIS:NIPAM=30:5:65) to a methanol solution of amine-containing gel particles and polymerizing the compound. [Diagram 36] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed and released per mass of amine-containing dry gel particles of a gas absorber obtained by adding a polymerizable compound (DMAPM:BIS=95:5) to an aqueous solution of amine-containing gel particles and polymerizing the compound. [Figure 37] 1 is a graph showing the change over time in the amount of carbon dioxide released from a gas absorbent having various amines added to a gel particle film made of amine-containing gel particles. [Figure 38] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed by a gas absorber in which various amines are added to a gel particle film made of amine-containing gel particles. [Figure 39] 1 is a graph showing the change over time in the amount of carbon dioxide released from a gas absorbent having various amines added to a gel particle film made of amine-containing gel particles. [Diagram 40] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed by a gas absorber in which various amines are added to a gel particle film made of amine-containing gel particles. [Diagram 41] 1 is a graph showing the change over time in the amount of carbon dioxide released from a gas absorber made of a gel particle membrane to which various concentrations of PMDETA aqueous solutions (0M, 1M, 3M, and 10M in terms of amine concentration) or PMDETA containing almost no water have been added to amine-containing dry gel particles. [Diagram 42] 1 is a graph showing the change over time in the amount of carbon dioxide absorbed by a gel membrane gas absorber in which various concentrations of PMDETA aqueous solutions (0M, 1M, 3M, and 10M in terms of amine concentration) or PMDETA containing almost no water has been added to amine-containing dry gel particles. [Diagram 43] 1 is a graph showing the amount of carbon dioxide released from a gas absorbent in the form of a gel film in which a 3N aqueous amine solution is added to amine-containing dry gel particles. [Diagram 44] 1 is a graph showing the amount of carbon dioxide released from a gas absorber that is a gel film in which 3N, 6N, and 8N aqueous amine solutions are added to amine-containing dry gel particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below. The following description of the constituent elements may be based on representative embodiments and specific examples, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "~" means a range including the numerical values ​​before and after "~" as the lower and upper limits. In this specification, "(meth)acrylamide" means "acrylamide" and "methacrylamide".

[0017] <Gas absorbing materials> The gas absorbing material of the present invention contains polymer compound particles having amino groups. When a small temperature change is applied to the polymer compound particles having amino groups, the swelling degree or internal structure of the particles or the acid dissociation constant of the amino groups change, and this change causes a change in the gas absorption ability. This allows the gas absorbing material to switch between a state in which the gas is absorbed and a state in which the gas is emitted. It is presumed that the switching between these two states is achieved by the following mechanism. In the following description, when a specific gas contained in the gas to be treated is absorbed and emitted, the specific gas may be referred to as the "target gas." First, when a gas is contacted with a polymer compound particle having an amino group at a specific temperature, the anion derived from the gas and the amino group of the polymer compound particle form a salt, and the polymer compound particle is in a state where the gas is reversibly absorbed. When the polymer compound particle is heated from this state, the swelling degree and internal structure of the particle, or the acid dissociation constant of the amino group, etc., change with a slight increase in temperature, and due to this change, the polymer compound particle becomes in a state where it is easy to emit gas. As a result, the gas is emitted from the polymer compound particle, and the amino group is regenerated in the polymer compound. If the polymer compound particle with the regenerated amino group is further cooled and heated to a specific temperature repeatedly, the cycle of the state of absorbing and emitting gas is repeated by the same mechanism as above. Because the polymer compound particles having amino groups have such functions, the gas absorption material of the present invention can be effectively used as a material for a gas absorbent that absorbs and dissipates gas, and can also reduce the amount of heat required for dissipation of gas. In addition, in the gas absorbing material of the present invention, since the polymer compound having an amino group is in the form of particles, when the deposited film on which the particles are deposited is exposed to the gas to be treated, the gas to be treated is absorbed on the surface of the deposited film, and the absorbed carbon dioxide molecules and bicarbonate ions diffuse into the film at high speed through the gaps between the particles. In addition, when the absorbed target gas is diffused, the carbon dioxide molecules and bicarbonate ions diffuse through the gaps between the particles at high speed, and the target gas is diffused from the surface of the deposited film, and a gas phase is generated in the gaps between the particles and diffused from the inside of the deposited film. Therefore, the gas absorber formed using this gas absorbing material has a large reversible absorption amount of gas per unit volume compared to a homogeneous gas absorber without voids, and can absorb and diffuse gas at a high speed.

[0018] In the gas absorbing material of the present invention, the gas to be absorbed and released is not particularly limited, but since it forms a salt with the amino group of the polymer compound particles and is easily absorbed by the particles, it is preferably an acidic gas such as carbon dioxide or hydrogen sulfide, and more preferably carbon dioxide. Since the gas absorbing material of the present invention can efficiently perform reversible absorption and release of gas by the above-mentioned mechanism, it can be effectively used for separation and recovery of acidic gas such as carbon dioxide or hydrogen sulfide, and can be particularly preferably used for separation and recovery of carbon dioxide, which has a large emission rate. In addition, unlike adsorbents, the gas absorbing material of the present invention can absorb a large amount of acidic gas even if a high concentration of water vapor is present in the gas. Therefore, for example, when treating a gas to be treated that contains water vapor and carbon dioxide, carbon dioxide can be directly separated and recovered without removing water vapor in advance, and the process required for treating the gas to be treated can be simplified. The amino group-containing polymer compound particles used in the gas absorbing material of the present invention will be described in detail below.

[0019] (Chemical structure and preparation of polymer particles containing amino groups) The polymer compound particles having an amino group are particles made of a polymer compound having an amino group, and are preferably composed only of a polymer compound having an amino group, but may also contain materials used in preparing the particles, such as particle size adjusting components such as surfactants, crosslinking agents, unreacted monomers, etc.

[0020] The polymer compound having an amino group is not particularly limited, but examples thereof include (meth)acrylamide polymers and derivatives thereof, polyethyleneimine and derivatives thereof, polyvinyl alcohol and derivatives thereof, polyallylamine and derivatives thereof, and the like. Specific constituent monomers include N,N-dimethylaminopropyl methacrylamide, N,N-diethylaminopropyl methacrylamide, N,N-dimethylaminoethyl methacrylamide, N,N-diethylaminoethyl methacrylamide, N,N-dimethylaminopropyl methacrylate, N,N-diethylaminopropyl methacrylate, N,N-dimethylaminoethyl methacrylate, N,N-diethylaminoethyl methacrylate, N,N-dimethylaminopropyl acrylamide, N,N-diethylaminopropyl acrylamide, N,N-dimethylaminoethyl acrylamide, N,N-diethylaminoethyl acrylamide, 3-aminopropyl methacrylamide hydrochloride, 3-aminopropyl acrylamide hydrochloride, N,N-dimethylaminopropyl acrylate, N,N-diethylaminopropyl acrylate, N,N-dimethylaminoethyl acrylate, N,N-diethylaminoethyl acrylate, 3-aminopropyl methacrylate hydrochloride, 3-aminopropyl acrylate hydrochloride, and the like, and an acrylamide polymer is preferable. The amino group of the polymeric compound having an amino group may be any of primary, secondary, and tertiary amino groups, but it is preferable that the acid dissociation constant of the conjugate acid changes in response to a stimulus such as a temperature change. In particular, it is preferable that the acid dissociation constant when absorbing carbon dioxide is equal to or larger than the acid dissociation constant of carbonic acid, and the acid dissociation constant when discharging carbon dioxide is equal to or smaller than the acid dissociation constant of carbonic acid. Among them, a tertiary amino group is preferable because it can increase the efficiency of discharging acidic gas, and a dialkylamino group such as a dimethylamino group is more preferable. In addition, the amino group of the polymeric compound may be bonded to the main chain or the side chain, but it is preferable that it is bonded to the side chain.

[0021] In addition, it is preferable that the polymer compound having an amino group has a hydrophobic group. This allows the polymer compound particles to undergo a significant change (phase transition) in swelling degree and internal structure in response to temperature changes, and gases such as carbon dioxide gas can be efficiently absorbed and released in response to temperature changes. In the following, the phase transition of the polymer compound particles having an amino group and a hydrophobic group will be described using the case where carbon dioxide is absorbed and released as a target gas as an example. Figure 1 is a schematic diagram showing the absorption and release cycle of carbon dioxide gas when the polymer compound particles having an amino group and a hydrophobic group are hydrogel particles. As shown in the upper left of Figure 1, at low temperatures, there is no steric hindrance around the amino group, and the amino group is in a state where it is easy to absorb acidic gas (high basicity). When the gel particle is contacted with the gas to be treated, which contains carbon dioxide gas, bicarbonate anions are generated by the nucleophilic attack of hydroxy anions on carbon dioxide, and one molecule of this bicarbonate anion forms a salt with one amino group. As a result, the gel particle is in a state where it has absorbed carbon dioxide gas. At the same time, the pH of the water decreases and the gel particle swells. When the gel particle is heated from this state, the hydrophobic interaction within the molecule increases, and the gel particle shrinks (phase transition). As a result, the amino group is covered with polymer chains with low polarity, which increases the steric hindrance, and the amino group is in a state where it is easy to emit acidic gas (low basicity). As a result, carbon dioxide gas is emitted, and at the same time, the pH of the water increases. Next, when the gel particle is cooled, the pH of the water increases further, and the gel particle swells and returns to its initial state. As described above, the gel particles of the polymer compound having amino groups and hydrophobic groups can be switched from an acid gas absorbing state to an acid gas discharging state by a slight temperature difference that causes a phase transition. Therefore, by using a gas absorbing material containing such gel particles, the amount of energy required for the separation and recovery process of acid gas can be reduced. The hydrophobic group to be introduced into the polymer compound is C X H 2X Or C X H 2X+1 Examples of the hydrocarbon group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a tert-butyl group, a pentyl group, a cyclopentyl group, an isopentyl group, a hexyl group, a cyclohexyl group, and the like. Of these, an isobutyl group and a tert-butyl group are more preferable. Alternatively, a hydroxyl group bonded to the above hydrophobic group, such as a hydroxyethyl group, a hydroxypropyl group, or a hydroxybutyl group, may be used.

[0022] The polymer compound having an amino group preferably has a polymer density within the particles in a dispersed state after the polymer compound particles are swollen in water of 0.3 to 80%, more preferably 1 to 60%.

[0023] The polymer compound particles having an amino group can be prepared using a solution containing a monomer component (hereinafter, these are referred to as "particle preparation liquid"). In this specification, "monomer component" refers to all monomers used in the synthesis of the polymer of the polymer compound particles having an amino group. The method for producing the polymer compound particles is not particularly limited, and conventionally known methods such as emulsion polymerization, dispersion polymerization, suspension polymerization, and seed polymerization can be used.

[0024] The monomer components used in the preparation of the particles preferably contain at least a monomer having an amino group, and further preferably contain a monomer having an amino group and a monomer not having an amino group. That is, the polymer compound having an amino group may be a homopolymer or copolymer of a monomer having an amino group, or may be a copolymer of a monomer having an amino group and a monomer not having an amino group. This allows the density of the amino group of the polymer compound particles to be adjusted to an appropriate range by controlling the ratio of these monomers. The monomer having an amino group and the monomer not having an amino group used as necessary are preferably substituted (meth)acrylamide monomers, more preferably substituted acrylamide monomers.

[0025] For the description and preferred range of the amino group of the monomer having an amino group, the description and preferred range of the amino group of the polymer compound having an amino group can be referred to. The number of amino groups that the monomer has is not particularly limited, and may be one or two or more. When the monomer has two or more amino groups, each amino group may be the same or different. The monomer having an amino group is not particularly limited, but examples thereof include N-(aminoalkyl)acrylamides and N-(aminoalkyl)methacrylamides, with N-(aminoalkyl)acrylamides being preferred.

[0026] The monomer component preferably contains a monomer having a hydrophobic group together with a monomer having an amino group. For the description and preferred range of the hydrophobic group of the monomer having a hydrophobic group, the description and preferred range of the hydrophobic group that can be adopted in the polymer compound having an amino group can be referred to. The hydrophobic group is preferably present at the terminal. The monomer having a hydrophobic group may or may not further have an amino group. The monomer having a hydrophobic group is not particularly limited, but examples thereof include N-alkylacrylamide, N-alkyl methacrylamide, N-alkyl acrylate, N-alkyl methacrylate, N,N-dialkylacrylamide, N-(hydroxyalkyl) methacrylamide, N,N-dialkyl acrylate, N-(hydroxyalkyl) methacrylate, N,N-dialkyl methacrylamide, N-(hydroxyalkyl) acrylamide, N,N-dialkyl methacrylate, N-(hydroxyalkyl) acrylate, and the like, with N-alkylacrylamide being preferred.

[0027] A preferred combination of a monomer having an amino group and a monomer having a hydrophobic group is a combination of N-(aminoalkyl)(meth)acrylamide and N-alkyl(meth)acrylamide, and a combination of N-(aminoalkyl)methacrylamide and N-alkylacrylamide is preferred. In particles made of a copolymer of N-(aminoalkyl)(meth)acrylamide and N-alkyl(meth)acrylamide, hydrophobic alkyl groups and hydrogen-bonding amides are uniformly distributed in the molecule in a well-balanced manner. Therefore, at low temperatures, the gel particles are easily dissolved in water and swollen, and efficiently absorb the gas contained in the gas to be treated. When heated from a state in which the gas has been absorbed, the gel particles shrink with a slight increase in temperature, and the gas absorption ability is significantly reduced, and the gas is efficiently diffused. Therefore, by using particles made of this copolymer as a gas absorption material, gas absorption and diffusion can be performed at a high speed, and the amount of heat required for gas diffusion can be reduced. In addition, the gel particles of this copolymer are unlikely to precipitate even when heated to a temperature above the phase transition temperature, and can maintain very stable solution properties.

[0028] The ratio of the monomer having an amino group in the monomer component is preferably 5 to 95 mol%, more preferably 30 to 70 mol%, and even more preferably 50 to 65 mol% based on the total moles of the monomer component. When the monomer component contains a monomer having a hydrophobic group, the molar ratio of the monomer having an amino group to the monomer having a hydrophobic group is preferably 95:5 to 5:95, and more preferably 2:1 to 1:2. Note that a monomer having both an amino group and a hydrophobic group is classified as a monomer having an amino group. The more amino groups there are, the higher the absorption ability of the polymer compound for acidic gas tends to be, but if there are too many amino groups, the particle shrinkage due to the high temperature and the emission of acidic gas are difficult to occur due to the electrical repulsion between the amino groups. By setting the ratio of the monomer having an amino group and the molar ratio of the monomer having an amino group to the monomer having a hydrophobic group within the above range, it is possible to obtain polymer compound particles in which a phase transition occurs easily by heating and acidic gas is efficiently emitted.

[0029] The particle preparation liquid may contain only the monomer component, or may contain other components. Examples of other components include a surfactant, a crosslinking agent, and a polymerization initiator. By using a surfactant, the particle size of the resulting polymer compound particles can be controlled by changing the concentration of the surfactant in the particle preparation liquid. In addition, by using a crosslinking agent, the swelling property of the particles can be controlled so that the polymer compound forms a crosslinked structure within the particles and does not swell excessively. In addition, when a relatively large amount of crosslinking agent is used or the monomer concentration during polymerization is set relatively high, a crosslinked structure can also be formed between the particles. As a result, a relatively large continuous void structure is formed between the composite particles connected by the crosslinked structure, and the absorption and emission of gas can be promoted. As the surfactant, a cationic surfactant such as cetyltrimethylammonium bromide can be used. The crosslinking agent may be any agent capable of forming a crosslinked structure between the monomers used, and N,N'-alkylenebisacrylamide is preferably used. The number of carbon atoms in the alkylene group of N,N'-alkylenebisacrylamide is not particularly limited, but is preferably 1 to 12, more preferably 1 to 4, and even more preferably 1 to 2. Instead of the alkylene group, oligoethyleneimine or oligoethylene glycol may be used as a crosslinking agent that functions as a crosslinking agent chain.

[0030] The solvent of the particle preparation liquid is not particularly limited, but examples thereof include polar solvents such as water, methanol, ethanol, isopropanol, acetonitrile, N,N-dimethylformamide, dimethylsulfoxide, etc., and may be a mixed solvent of two or more of these polar solvents. Among these, it is preferable to use water or a mixed solvent of water and another polar solvent.

[0031] (Properties of Amino Group-Containing Polymer Compound Particles) The polymer compound particles having amino groups may be gel particles swollen with a liquid or dry particles (solid particles), but are preferably gel particles. In the case of gel particles, gas is dissolved in the liquid contained in the gel particles, so that the amino groups inside the gel particles can also contribute to the absorption of gas. This allows a large reversible absorption amount of gas to be obtained.

[0032] The polymer compound particles preferably have a particle size of 5 nm to 10 μm in a dry state. The hydrodynamic particle size of the polymer compound particles after swelling in water is preferably tens of nm to several tens of μm, more preferably 10 nm to 50 μm, and even more preferably 20 nm to 10 μm, as measured by dynamic light scattering. The "particle size after swelling in water" of the polymer compound particles refers to the particle size of the dried polymer compound particles after immersing them in water for 24 hours, and is the average particle size measured by dynamic light scattering. When the particle size of the polymer compound particles when dry and the particle size after swelling are within the above ranges, the reversible gas absorption amount per unit volume, and the gas absorption rate and emission rate can be sufficiently increased.

[0033] The liquid contained in the gel particles is not particularly limited, and examples thereof include polar solvents such as water, methanol, ethanol, isopropanol, acetonitrile, N,N-dimethylformamide, and dimethylsulfoxide, and may be a mixed solvent of two or more of these polar solvents. Among them, it is preferable to use water or a mixed solvent of water and another polar solvent. That is, it is preferable that the gel particles are hydrogel particles. By using hydrogel particles as the gel particles, gas can be efficiently dissolved in the particles, and a larger volume of gas can be reversibly absorbed. The water content in the gel particles is preferably 0.1 mL or more, more preferably 0.5 mL or more, and even more preferably 1 mL or more per 1 g of solid content. The water content in the gel particles is preferably 20 mL or less, more preferably 10 mL or less, and even more preferably 8 mL or less. By setting the water content in the gel particles within the above range, the gel particles are prevented from swelling excessively, and gas can be sufficiently dissolved in the gel particles, thereby increasing the amount of gas absorbed and emitted.

[0034] The polymer compound particles having an amino group used in the present invention preferably change their gas absorption ability in response to a stimulus such as a temperature change. Examples of factors that change the gas absorption ability include a change in the acid dissociation constant of the functional group, a change in the three-dimensional structure, a change in the swelling degree, a change in hydrophilicity, a change in the water content, a change in the amount of dissolved bicarbonate ions, and a change in the amount of dissolved hydrogen sulfide ions. The polymer compound particles having an amino group may change their gas absorption ability due to any factor, but it is preferable that the gas absorption ability changes at least due to a change in the acid dissociation constant of the ammonium ion, which is the conjugate acid of the amino group, in response to a temperature change. In particular, it is preferable that the change in the acid dissociation constant is caused by the swelling and shrinkage (volume phase transition) of the gel in response to a temperature change, the coil-globule structure transition of the polymer in response to a temperature change, or a change in the hydrophilicity and hydrophobicity of the molecule. As a result, the mechanism shown in FIG. 1 allows the gas absorption ability of the polymer compound particles to be greatly changed by a small temperature change, and the amount of energy required for gas absorption and emission can be reduced.

[0035] The phase transition temperature of the polymer compound particles is preferably 10 to 95°C, more preferably 20 to 90°C, and even more preferably 30 to 80°C. In this specification, the term "phase transition temperature" refers to the temperature at which the acid dissociation constant of the ammonium ion, which is the conjugate acid of the amino group, becomes equal to or smaller than the acid dissociation constant of carbonic acid, or the temperature at which the particle size of the polymer compound particles in water becomes 30% or more smaller than the particle size at 5°C. This phase transition temperature can be determined by immersing the polymer compound particles in water at 5°C, and measuring the pH or particle size of the polymer compound particle aqueous solution at regular temperature intervals or continuously in parallel with the water temperature being raised from 15°C. The particle size of the polymer compound particles can be measured by dynamic light scattering.

[0036] <Gas absorber> The gas absorber of the present invention comprises a gel particle membrane made of a polymer compound having an amino group, and a carrier for supporting the gel particle membrane. The gel particle membrane used in the present invention is a membrane containing gel particles obtained by swelling solid particles of a polymer compound having an amino group with water. The gel particle membrane can be confirmed by adding fluorescently modified gel particles to visualize the gel particle membrane and observing the gel particle membrane with a focusing laser microscope. The fluorescent modification of the gel particles can be performed by introducing 4-Acrylamidofluorescein, etc. The gel particle film may be a particle deposition film in which gel particles are deposited on a carrier to form a layer, or may be a film in which gel particles are embedded between fibers or in pores constituting the carrier to form a layer. For the description and preferred range of the polymer compound having an amino group and the gel particles thereof, the description and preferred range of the polymer compound having an amino group and the gel particles thereof in the gas absorption material can be referred to.

[0037] The gel particle film can be formed, for example, by applying a particle solution in which a polymer compound particle having an amino group is dissolved in a polar solvent onto a carrier, drying the solution to form a solid polymer compound particle film, and adding water to the polymer compound particle film to swell it. At this time, a polymerizable compound and a polymerization initiator may be added to the particle solution, and the polymerizable compound may be polymerized after application and drying, and then water may be added to swell it. For the polymerizable compound to be added, the explanation of the stabilizer described later can be referred to. The polymerization initiator may be any one that can initiate polymerization of the polymerizable compound, and may be a photopolymerization initiator or a thermal polymerization initiator. A photopolymerization initiator is preferable. When a photopolymerization initiator is used, polymerization is initiated by irradiating with active energy rays such as ultraviolet rays. By performing such polymerization, a gel particle film that is highly stable and does not swell excessively can be produced. As the polar solvent for the particle solution, any of the polar solvents exemplified as those to be contained in the gel particles can be used, and among them, it is preferable to use water or a mixed solvent of water and another polar solvent. The content of water in the gel particle film is preferably 10% by mass or more, more preferably 50 to 2000% by mass, based on the total amount of the gel particle film. The thickness of the gel particle film is not particularly limited, but is preferably 1 to 1000 μm, more preferably 10 to 600 μm, and even more preferably 20 to 400 μm. By setting the thickness of the gel particle film within the above range, the reversible absorption amount of gas per unit volume can be made sufficient, and the gas can be absorbed and diffused at a high speed. When the gel particles form a layer in a state where they are embedded between the fibers constituting the carrier or in the pores, the thickness of the gel particle layer on the fiber surface or pore surface corresponds to the thickness of the gel particle film.

[0038] The gel particle membrane has a carbon dioxide gas diffusion rate of 0.1 mmol / m 2 / sec or more, and 0.15 mmol / m 2 / sec or more is more preferable, and 0.2 mmol / m 2 / sec or more. Also, it is preferable that the absorption rate is 0.05 mmol / m 2 / sec or more, and 0.1 mmol / m 2 / sec or more is more preferable, and 0.2 mmol / m 2 It is more preferable that the rate is 1 / sec or more. In this specification, the "carbon dioxide gas absorption rate of the gel particle membrane" is determined by measuring the amount of carbon dioxide in the outlet gas using gas chromatography or an infrared carbon dioxide concentration meter when nitrogen gas (mixed gas) containing 10% carbon dioxide is humidified and passed over the surface of the gel particle membrane at 60° C. In addition, the above-mentioned diffusion rate and absorption rate are the results for the gel particle membrane when 5 mol % of DMAPM is introduced, and will be even greater when the amount of DMAPM is large or when a promoter is added.

[0039] [Components other than polymer particles having amino groups] The gel particle film may contain polymer compounds other than the polymer compound having an amino group, and additives. The polymer compound other than the polymer compound having an amino group is not particularly limited, but is preferably a polymer compound that reacts to a stimulus such as a temperature change, etc. Examples of the reaction to a stimulus include a change in the acid dissociation constant of the functional group, a change in the three-dimensional structure, a change in the degree of swelling, a change in hydrophilicity, a change in the water content, a change in the amount of dissolved bicarbonate ions, and a change in the amount of dissolved hydrogen sulfide ions.

[0040] Examples of additives include membrane stabilizers, absorption promoters, diffusion promoters, and the like. Examples of the membrane stabilizer include polymer compounds, polymerizable molecules (polymerizable compounds), crosslinking agents such as titanium crosslinking agents, primary amines, secondary amines, etc. Among these, preferred polymer compounds include polymer compounds having a primary amino group such as polyvinylamine, polymer compounds having a secondary amino group, polymer compounds having a tertiary amino group, polymer compounds having multiple types of primary amino groups, secondary amino groups, and tertiary amino groups, polyvinyl alcohol, polyethylene, polyvinyl alcohol / polyethylene copolymers, etc. In addition, when a polymerizable molecule is used as the membrane stabilizer, the polymer compound generated by the polymerization reaction of this molecule in the gel particle membrane also functions as a membrane stabilizer. This makes it easier to maintain a uniform membrane shape without excessive swelling even after water is added after membrane formation or after gas absorption and dissipation. Examples of the polymerizable molecule include monomers having a polymerizable group, such as acrylic monomers. Among them, acrylamide or an acrylamide derivative can be preferably used. For example, alkylacrylamide, substituted or unsubstituted aminoalkylacrylamide, acrylamide derivatives having two polymerizable groups, etc. can be mentioned, and among these, substituted aminoalkylacrylamide and acrylamide derivatives having two polymerizable groups can be preferably used. It is preferable to use a combination of substituted aminoalkylacrylamide and acrylamide derivatives having two polymerizable groups, and the molar fraction is preferably 60 to 99: 40 to 1, more preferably 80 to 99: 20 to 1, and even more preferably 90 to 99: 10 to 1. Specific examples of monomers having a polymerizable group include N-isopropylacrylamide (NIPAM), tert-butylacrylamide (TBAM), N,N-dimethylaminopropyl methacrylamide (DMAPM), N,N'-methylenebisacrylamide (BIS), acrylamide, etc. These polymerizable compounds may be used alone or in combination of two or more. When two or more are used in combination, a preferred example is a combination of N,N-dimethylaminopropyl methacrylamide (DMAPM) and N,N'-methylenebisacrylamide (BIS). The content of the membrane stabilizer in the gel particle membrane is preferably 1 to 89% by mass based on the total amount of the gel particle membrane.

[0041] The absorption promoter is a compound having a function of promoting the absorption of an acidic gas into the gel particle film. The diffusion promoter is a compound having a function of promoting the diffusion of an acidic gas from a polymer compound particle. In the present invention, it is preferable to use an absorption diffusion promoter having both the functions of an absorption promoter and a diffusion promoter. Each of these absorption promoters, diffusion promoters, and absorption diffusion promoters may also function as a film stabilizer. The total content of the absorption promoter, diffusion promoter, and absorption diffusion promoter in the gel particle film is preferably 1 to 20 mass% based on the total amount of the gel particle film. The content of the absorption promoter in the gel particle film is preferably 0.1 to 12N, more preferably 1 to 10N, and even more preferably 3 to 9N, in terms of amine concentration. As the absorption promoter, diffusion promoter, and absorption diffusion promoter, low molecular weight amines can be preferably used. The molecular weight of the low molecular weight amine is preferably 61 to 10,000, more preferably 75 to 1,000, and even more preferably 90 to 500. The boiling point of the low molecular weight amine is preferably 80°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher, because it can be used repeatedly and is practical.

[0042] The low molecular weight amine may contain any of primary amino groups, secondary amino groups, and tertiary amino groups, and may contain multiple amino groups, preferably 1 to 3. The secondary amino group and the tertiary amino group may be cyclic amino groups. Furthermore, the low molecular weight amine may contain functional groups other than amino groups, for example, hydroxyl groups. The low molecular weight amine preferably contains 0 to 2 hydroxyl groups. Examples of preferred low molecular weight amines include amines having an amino group and a hydroxyl group, and amines having three amino groups, and more preferred low molecular weight amines include amines having a secondary amino group and a hydroxyl group. In particular, amines having a secondary amino group and a hydroxyl group with a boiling point of 150° C. or more are preferred because they can dramatically increase the amount of acidic gas emitted in a high concentration range and are suitable for repeated use. The low molecular weight amine may be specifically exemplified by the compound represented by the following formula: The absorption and diffusion promoter used in Example (9) may also be preferably used.

[0043] [ka]

[0044] Among these, it is preferable to use DMAE, IPAE, Bis(2DMAE)ER, 1-2HE-PRLD, 1-2HE-PP, TM-1,4-DAB, TMHAD, and PMDETA, since they can increase the amount of acidic gas emitted. Among these, it is more preferable to use IPAE, Bis(2DMAE)ER, 1-2HE-PP, TM-1,4-DAB, TMHAD, and PMDETA, since they have a relatively high boiling point and are difficult to evaporate. It is even more preferable to use IPAE, TM-1,4-DAB, TMHAD, and PMDETA, since the amount of acidic gas emitted can be significantly increased by increasing the concentration. It is particularly preferable to use IPAE, TMHAD, and PMDETA, since they are easily available. Furthermore, it is most preferable to use IPAE, since it can dramatically increase the amount of acidic gas emitted, especially in a high concentration range, and it is possible to increase the amount of acidic gas emitted even in a situation where the amount of water relative to the amine is small. The additives described above may be used alone or in combination of two or more.

[0045] The gel particle film thus constructed reversibly absorbs gas under certain conditions, dissipates the gas in response to a stimulus such as a temperature change, and then reversibly absorbs the gas when the certain conditions are restored or another stimulus is applied. Examples of gases that the gel particle film reversibly absorbs include acidic gases such as carbon dioxide and hydrogen sulfide, and water vapor.

[0046] [Carrier] The gas absorbent of the present invention is also characterized in that the gel particle membrane is supported by a carrier. Gel membranes have lower fluidity than liquids, making convection difficult to occur. As a result, the rate-limiting step in the absorption process of acidic gases in gel membranes is the diffusion process of the ions, and ion diffusion from the membrane surface to a depth of several hundred micrometers or more is restricted, which limits the amount of acidic gas that the gel membrane can absorb. On the other hand, when the gel particle membrane is supported on an appropriate carrier, the gas to be treated can diffuse into the membrane through the gaps between the particles, and the acid gas can diffuse from the membrane. Heat is efficiently transferred to the gel particle membrane through the carrier, so that the temperature of the entire gel particle membrane changes responsively to changes in the external temperature. By stacking the carriers, a large number of gel particle membranes with a thickness of several hundred μm or less can be packed into a reactor of a certain volume. As a result, the absorption and emission rates of acid gas and water vapor gas are increased, and the acid gas diffuses deep into the membrane, so that a large amount of gas can be absorbed. In addition, by being supported on a carrier, the gel particle membrane is less likely to collapse, and the shape of the gel particle membrane can be stably maintained. Furthermore, a large amount of gas can be reversibly absorbed in a reactor of a certain volume.

[0047] The carrier may be a thin plate or a fiber assembly. In the present invention, the term "thin plate" refers to a flat plate, sheet, or foil having a thickness of 2 mm or less and 5 μm or more. The material of the thin plate has a specific heat at constant pressure of 2500KJ / (m 3 It is preferable that the thermal conductivity of the thin plate is 10 W / (mK) or less, and that the thermal conductivity of the thin plate is 10 W / (mK) or more. A thin plate having such thermal properties changes temperature responsively in response to changes in the external temperature, and can efficiently transmit the temperature change to the entire gel particle film. In this specification, the term "constant pressure specific heat" refers to a value measured by a calorimeter such as a water calorimeter or a differential scanning calorimeter, and the term "thermal conductivity" refers to a value measured by a laser flash method or a steady heat flow method.

[0048] As the thin plate, a metal thin plate (metal foil), a sheet made of a carbon material, a carbon sheet, a resin film (polymer compound film), etc. can be used. As the sheet made of a carbon material, a graphite sheet, etc. can be exemplified, and as the resin film, polyethylene, polypropylene, PET, polyimide, etc. can be exemplified. As the thin plate, an aluminum thin plate, an iron thin plate, or a graphite sheet is preferably used because of its high thermal conductivity. Alternatively, an aluminum thin plate, a graphite sheet, or a resin film is preferably used because of its low specific heat. As the metal thin plate, a stainless steel thin plate, an iron thin plate, an aluminum thin plate, or a nickel thin plate can be exemplified. Among these, an iron thin plate, an aluminum thin plate, or a nickel thin plate is preferably used because of its relatively high thermal conductivity, and a nickel thin plate is more preferably used.

[0049] The thin plate may be a plate having a homogeneous internal structure, or may be a porous body or a honeycomb structure. In the case of a porous body or a honeycomb structure, the pores can be filled with a gel particle film, so that the heat of the thin plate can be easily transferred to the gel particle film, and the responsiveness of the gas absorber to temperature changes can be improved. In particular, porous bodies such as foamed metal, foamed nickel, and porous carbon have high heat conductivity to the gel particle film, and by using them as a carrier, the responsiveness of the gas absorber to temperature changes can be greatly improved. The pore size of the porous body such as foamed metal is preferably 0.1 to 10 mm, more preferably 0.4 to 4 mm. In addition, the specific surface area is 100 to 10,000 m 2 / m 3 Preferably, the thickness is 200 to 6000 m. 2 / m 3 It is more preferable that the carrier is made of a porous resin or porous carbon. The carrier has a small heat capacity, so that the thermal efficiency of the absorber can be improved. The porous body used as the carrier preferably has a porosity of 1 to 99%, more preferably 10 to 99%, and even more preferably 20 to 95%. In this specification, the "porosity of the thin plate" means the porosity measured by the apparent volume and mass of the thin plate and the density of the material. The carrier may also be a laminate of a plurality of these thin plates. In the laminate, all the thin plates may be the same, or a plurality of thin plates of different materials or thicknesses may be combined.

[0050] The fiber assembly is a material obtained by processing a large number of fibers into a thin, wide plate shape. Examples of the fiber assembly include cloth and paper, and among them, it is preferable to use a porous one such as a filter. The cloth may be any of woven cloth, felt, and nonwoven cloth. Sintered metal fiber felt can also be preferably used as a carrier. This has a shape in which fibers, which are sintered fiber bodies, are densely assembled, and high heat conductivity can be obtained. For example, sintered felt made of stainless steel fibers or sintered felt made of nickel fibers can be preferably used, and among them, sintered felt made of nickel fibers can be particularly preferably used. The fibers used in the fiber assembly have a specific heat at constant pressure of 2500KJ / (m 3 It is preferable that the fiber aggregate has a thermal conductivity of 10 W / (mK) or less, and a thermal conductivity of 10 W / (mK) or more. A fiber aggregate having such thermal properties changes temperature responsively in response to changes in the external temperature, and can efficiently transmit the temperature change to the entire gel membrane.

[0051] The fibers used in the fiber assembly may be inorganic fibers, organic fibers, or composite fibers that combine inorganic and organic fibers. Examples of inorganic fibers include stainless steel fibers, aluminum fibers, metal fibers such as nickel fibers, and carbon fibers, and nickel fibers are preferred because they provide high thermal conductivity. Examples of organic fibers include natural fibers such as cotton and hemp, and synthetic fibers such as rayon and polyester. The diameter of the fibers is not particularly limited, but is preferably 8 to 100 μm, which makes it possible to obtain a gel particle membrane having excellent gas absorption and diffusion properties. The carrier may be an assembly in which a plurality of these fiber assemblies are laminated. In the assembly, each fiber assembly may be the same, or a plurality of fiber assemblies having different fiber types, fiber diameters, fiber densities, etc. may be combined. The carrier may be a laminate in which a thin plate and a fiber assembly are laminated.

[0052] When a fiber assembly is used as a carrier, the filling rate of the gel particle membrane is preferably 10 to 100%, more preferably 15 to 80%, and further preferably 20 to 70%. The filling rate of the gel particle membrane here refers to the occupancy rate of the gel particle membrane with respect to the total volume of the gas absorbent. This allows the gel particle membrane to efficiently absorb and dissipate gas. In particular, if a sintered body is used, it is possible to maintain high gas absorption and dissipation capacity of the gel particle membrane even at a high filling rate. For example, it is possible to maintain high gas absorption and dissipation capacity even at a filling rate of 60% or more.

[0053] The shape of the carrier is not particularly limited and can be appropriately selected depending on the application. Specific examples of the shape of the carrier include a plate shape and a cylinder shape, and the planar shape of the plate and the cross-sectional shape of the cylinder may be any of a polygonal shape such as a square shape or a rectangle shape, a perfect circle shape, an ellipse shape, and the like.

[0054] <Gas absorption method> The gas absorption method of the present invention is a method of absorbing gas into amino groups in a gel particle membrane. For an explanation of the gel particle membrane of a polymer compound having an amino group, the explanation of the gel particle membrane in the above <Gas absorber> can be referred to. When the amino groups inside the gel particle membrane come into contact with a gas at a certain temperature, the acid derived from the gas reacts with the base derived from the amino groups of each gel particle to form a salt, thereby enabling the gas to be absorbed efficiently. In addition, the gas can be dissipated from the gel particle film by increasing the temperature of the gel particle film. When the temperature of the gel particle film is increased, the basicity inside the gel particle film decreases. In addition, the conjugate acid pKa of the amine in the gel particle film decreases. Furthermore, the hydrophobic interaction of each gel particle increases, and each gel particle shrinks, that is, a volume phase transition occurs in the gel particle, and the steric hindrance around the amino group increases. As a result, the gas is dissipated from the gel particle film. After that, when the temperature of the gel particle film is decreased, the basicity inside the gel particle film increases. In addition, the conjugate acid pKa of the amine in the gel particle film increases. Furthermore, the particles swell again, and the gel particle film returns to the state before the phase transition. The gel particle membrane, which has returned to a more basic state, can absorb gas again, and then when the temperature is raised, the absorbed gas is released by the same mechanism as above. The temperature is then repeatedly lowered and raised, and the cycle of gas absorption and release is repeated in synchronization with this. By repeating this gas absorption and release, it becomes possible to separate and recover a specific gas, for example, from a large volume of exhaust gas. For detailed mechanisms of the phase transition of gel particles and the absorption and desorption of gas, please refer to Figure 1 and the explanation of Figure 1 in the section "Gas Absorbing Material." In order to absorb and dissipate gas by such a mechanism, it is important to raise the temperature of the gel particle film that has absorbed the gas until the basicity is reduced. In particular, it is important to raise the temperature until the basicity is equal to or lower than the pKa of carbonic acid. If the temperature is not raised sufficiently, the gas absorbed in the gel particle film cannot be sufficiently dissipated, and the subsequent gas absorption rate, dissipation rate, and reversible absorption amount become small. For example, when the gel particles are gel particles of a (meth)acrylamide-based polymer, the temperature of the gel particle film during gas absorption is preferably 1 to 60°C, and the temperature of the gel particle film during gas dissipation is preferably 40 to 200°C.

[0055] <Applications of gas absorbers> As described above, the gas absorber of the present invention can absorb and release gases such as carbon dioxide at high speed and has a large gas absorption capacity, and therefore can be suitably used as a gas absorber for acidic gas absorption devices, acidic gas recovery devices, water vapor absorption devices, water vapor recovery devices, etc. In addition, the gas absorber of the present invention can be effectively applied to heat exchangers and heat recovery devices, since the carrier can also function as the heat transfer surface of a heat exchanger or as the heat exchanger itself. In this case, for example, a gel-like film is provided on the carrier surface (the surface of the heat transfer surface) that functions as the heat transfer surface.

[0056] In the following, a first embodiment and a second embodiment of a carbon dioxide gas recovery apparatus will be described as an example of an acid gas recovery apparatus to which the gas absorber of the present invention is applied. Fig. 2 is a schematic diagram showing the carbon dioxide gas recovery apparatus of the first embodiment, and Fig. 3 is a schematic diagram showing the carbon dioxide gas recovery apparatus of the second embodiment.

[0057] As shown in Fig. 2, the carbon dioxide gas recovery device of the first embodiment includes a heat exchanger 21, a desulfurizer 22, a cylindrical gas absorber 23, and first to third pipes 24, 25, and 26 connected to each of these parts. One end of the first pipe 24 is a gas inlet for introducing exhaust gas (gas to be treated), and the other end is connected to the desulfurizer 22. One end of the second pipe 25 is connected to the desulfurizer 22, and the other end is connected to one side of the gas absorber 23. The third pipe 26 has a circulation path 26a connected to one side and the other side of the gas absorber 23, and a branch path 26b branching from the circulation path 26a on the one side of the gas absorber 23, and one end of the branch path 26b is a gas outlet for discharging the recovered carbon dioxide gas. The connecting portions of the second pipe 25 and the third pipe 26 on one side surface of the gas absorber 23 are provided on approximately the same diameter of the circular side surface so as to sandwich the center. The heat exchanger 21 is connected to the middle part of the first pipe 24 and the middle part of the circulation path 26a. The gas absorber 23 is made of the gas absorber of the present invention. In this embodiment, the gas absorber 23 has a carrier made of a cylindrical honeycomb rotor made by processing a fiber aggregate into a honeycomb shape, a gel particle film supported on the carrier, and is configured to be continuously rotated around the center of the disk as the rotation axis. When the carbon dioxide gas device is turned off, the gas absorber 23 is at a temperature approximately equal to the ambient temperature.

[0058] To recover carbon dioxide gas from exhaust gas using this acid gas recovery device, the operation of each part is turned on, and the high-temperature exhaust gas after dust collection is introduced from one end of the first pipe 24. The introduced exhaust gas passes through the first pipe 24 and is introduced into the desulfurizer 22, which has a cooling capacity of about 30°C. Here, the desulfurizer and the cooler may be separate devices. When passing through the first pipe 24, part of the heat of the exhaust gas is transferred to the circulation path 26a of the third pipe 26 via the heat exchanger 21, and the gas in the circulation path 26a is heated to about 75°C. The exhaust gas introduced into the desulfurizer 22 is desulfurized in the desulfurizer 22 and then flows into the second pipe 25. The mixed gas that flows into the second pipe 25 has a temperature of about 30°C, and is introduced into the gas absorber 23 at about this temperature. In the gas absorber 23, since the temperature of the mixed gas is about 30°C, carbon dioxide is efficiently absorbed by the gel particle film in the region where the mixed gas comes into contact, and gases other than carbon dioxide gas are discharged to the outside of the gas absorber 23. Meanwhile, the region of the gas absorber 23 where carbon dioxide has been absorbed moves to the vicinity of the connection part of the third pipe 26 by the rotation of the gas absorber 23, and comes into contact with the gas introduced from the circulation path 26a of the third pipe 26. Since the gas introduced from the circulation path 26a is heated to about 75°C by heat exchange with the exhaust gas, the gel particle film undergoes a phase transition in the gas absorber 23 in the region where the gas comes into contact, and carbon dioxide gas is dissipated. A part of the dissipated carbon dioxide gas flows into the branch path 26b of the third pipe 26, and is discharged to the outside from the gas outlet of the branch path 26b and collected. Another part of the dissipated carbon dioxide gas flows into the circulation path 26a of the third pipe 26. The carbon dioxide that has flowed into the circulation path 26a is heated by the heat exchanger 21 midway through the circulation path 25a, and then is reintroduced into the gas absorber 23, and the heat is used to heat the gel particle film.

[0059] As described above, in the carbon dioxide gas recovery device of the first embodiment, the heat of the exhaust gas is reused to heat the gas absorber, and switching is performed from a state in which acid gas is absorbed to a state in which it is released. In this embodiment, the heat of the exhaust gas is effectively utilized, so the amount of energy consumed in the carbon dioxide gas separation and recovery process can be significantly reduced. In the first embodiment, if the temperatures of the exhaust gas and the absorber cannot be controlled to a temperature suitable for the absorption and release of carbon dioxide, the temperature control is improved by adding an external heat exchange mechanism or an additional heating mechanism to the piping and the absorber.

[0060] Next, a second embodiment of the carbon oxide gas recovery device will be described. As shown in FIG. 3, the acid gas recovery apparatus of the second embodiment includes a first heat exchanger 31, a second heat exchanger 32, a desulfurizer 33, a first tank 34, a second tank 35, and a first pipe 36 and a second pipe 37 connected to each of these parts. One end of the first pipe 36 is a gas inlet for introducing exhaust gas (gas to be treated), and the other end is connected to the desulfurizer 33 having a cooling capacity. Here, the desulfurizer and the cooler may be separate devices. The second pipe 37 has a main path 37a, one end of which is connected to the desulfurizer 33, and a first path 37b and a second path 37c branched at the other end of the main path 37a. One end of the first path 37b is connected to the main path 37a, and the other end is connected to the first tank 34. One end of the second path 37c is connected to the main path 37a, and the other end is connected to the second tank 35. Valves (not shown) for opening and closing each of the first and second paths 37b, 37c are provided near the other ends of the first and second paths 37b, 37c. The first heat exchanger 31 is connected to a first intermediate portion of the first pipe 36 and the first tank 34, and the second heat exchanger 32 is connected to a second intermediate portion of the first pipe 36 and the second tank 35, respectively. In the carbon dioxide gas recovery device of the second embodiment, gel particle membranes 38, 39 are applied to the heat exchange surface of the first heat exchanger 31 in the first tank 34 and the heat exchange surface of the second heat exchanger 32 in the second tank 35, respectively. In this embodiment, the first heat exchanger 31 in the first tank 34 and the second heat exchanger 32 in the second tank 35, and the gel particle membranes 38, 39 loaded in these tanks constitute the gas absorber of the present invention, and function as an absorption tower and a diffusion tower for carbon dioxide gas, respectively. The gel particle membranes 38, 39 in each tank 34, 35 are at a temperature similar to the ambient temperature (about 30°C) when the operation of the carbon dioxide gas recovery device is OFF.

[0061] To recover carbon dioxide gas from exhaust gas using this carbon dioxide gas recovery device, first, the valve of the first path 37b of the second pipe 37 is opened, the valve of the second path 37c of the second pipe 37 is closed, the first heat exchanger 31 is turned off, and the second heat exchanger 32 is turned on. In this state, the first tank 34 functions as an absorption tower. That is, in this state, when the high-temperature exhaust gas after dust collection is introduced from one end of the first pipe 36, the introduced exhaust gas passes through the first pipe 36 and is introduced into the desulfurizer 33. When passing through the first pipe 36, part of the heat of the exhaust gas is transferred to the second tank 35 via the second heat exchanger 32, and the exhaust gas is cooled. The exhaust gas introduced into the desulfurizer 33 is subjected to desulfurization treatment in the desulfurizer 33 having a cooling capacity, and after being further cooled, flows into the main path 37a of the second pipe 37. The mixed gas that has flowed into the main path 37a is at about 30°C, and is introduced into the first tank 34 via the main path 37a and the first path 37b at about this temperature. In the first tank 34, since the temperature of the mixed gas is about 30°C, carbon dioxide is efficiently absorbed into the gel particle film 38, and gases other than carbon dioxide are discharged to the outside from a gas exhaust port provided in the first tank 34.

[0062] After the carbon dioxide is sufficiently absorbed in the gel particle film 38, the valve of the first path 37b of the second pipe 37 is switched to a closed state, the valve of the second path 37c of the second pipe 37 is switched to an open state, the first heat exchanger 31 is switched to an ON state, and the second exchanger 32 is switched to an OFF state. As a result, the heat of the exhaust gas passing through the first pipe 36 is transferred to the first tank 34 and the gel particle film 38 via the first heat exchanger 31. The gel particle film 38 in the first tank 34 is heated to about 75°C by the heat from the first heat exchanger 31, and dissipates carbon dioxide gas. The dissipated carbon dioxide gas is discharged from a gas outlet provided in the first tank 34 and collected. Meanwhile, the mixed gas of about 30°C that flows into the second pipe 37 via the same path as above is introduced into the second tank 35 via the second path 37c, and carbon dioxide is absorbed by the gel particle film 39 loaded in the tank 35. That is, in this state, the first tank 34 functions as a diffusion tower, and the second tank 35 functions as an absorption tower, and the absorption and diffusion of carbon dioxide gas are carried out in parallel.

[0063] After the carbon dioxide gas is sufficiently diffused from the gel particle membrane 38 and absorbed into the gel particle membrane 39, as shown in FIG. 3, the valve of the first path 37b of the second pipe 37 is opened, the valve of the second path 37c of the second pipe 37 is closed, the first heat exchanger 31 is turned off, and the second heat exchanger 32 is turned on, so that the first tank functions as an absorption tower and the second tank functions as a diffusion tower. As a result, the absorption and diffusion of carbon dioxide gas are performed in parallel in the towers opposite to those before the switching. Furthermore, by repeatedly performing the above-mentioned switching operation, the absorption and diffusion of carbon dioxide gas from the exhaust gas can be performed continuously, and carbon dioxide gas can be efficiently separated and recovered from a large amount of exhaust gas.

[0064] As described above, in the carbon dioxide gas recovery device of the second embodiment, the heat of the exhaust gas is reused to cause a phase transition in the gas absorber, and switching is performed from a state in which the acid gas is absorbed to a state in which the acid gas is released. Therefore, the energy utilization efficiency can be greatly improved compared to the case where the conventional carbon dioxide gas separation and recovery process is used. In the second embodiment, if the temperature of the exhaust gas and the absorber cannot be controlled to a temperature suitable for absorbing and releasing carbon dioxide, the temperature control is improved by adding a heat exchange mechanism with the outside or an additional heating mechanism to the piping and the absorber. EXAMPLES

[0065] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.

[0066] [I] Synthesis of amine-containing gel particles Amino group-containing polymer compound particles were synthesized as follows. In the following description, the gel of amino group-containing polymer compound particles is sometimes referred to as "amine-containing gel particles," and the particles obtained by drying the "amine-containing gel particles" are sometimes referred to as "amine-containing dried gel particles."

[0067] (Synthesis Example 1) One liter of pure water was added to a 2-liter three-neck flask and heated to 70°C. 2 mM of surfactant (cetyltrimethylammonium bromide) and three types of monomers were dissolved in the flask to a total monomer concentration of 312 mM. The composition of the three types of monomers was 55 mol% N-(dimethylaminopropyl) methacrylamide, 43 mol% N-tert-butylacrylamide, and 2 mol% N,N'-methylenebisacrylamide. N-(dimethylaminopropyl) methacrylamide was used after removing the polymerization inhibitor with an alumina column. N-tert-butylacrylamide was dissolved in a small amount of methanol in advance to make a 0.68 g / mL solution, which was then added. The mixture was kept at 70°C and stirred with a mechanical stirrer, and nitrogen gas was bubbled through the mixture for 1 hour to remove oxygen from the system. To the monomer solution thus obtained, a solution of 700 mg of 2,2'-azobis(2-methylpropionamidine)dihydrochloride dissolved in 5 mL of pure water was added, and the mixture was reacted at 70°C for 3 hours under a nitrogen atmosphere. After the reaction, the precipitate was filtered, and the unreacted monomer and surfactant were removed by dialysis for 3 days using a dialysis membrane (MWCO 12-14.000, width: 75 mm, vol / length: 18 mL / mL) [Spectrum Laboratories]. The counter anion was removed from the precipitate after dialysis using a strongly basic ion exchange resin, and amine-containing gel particles were obtained. The same experiment was performed on materials that were not subjected to dialysis or ion exchange, and it was confirmed that they had almost the same functions. The particle size of the obtained amine-containing gel particles was 800 nm.

[0068] (Synthesis Example 2) Amine-containing gel particles were obtained in the same manner as in Synthesis Example 1, except that N-isopropylacrylamide was used instead of N-tert-butylacrylamide and the composition of the three monomers was changed to 5 mol% N-(dimethylaminopropyl)methacrylamide, 93 mol% N-isopropylacrylamide, and 2 mol% N,N'-methylenebisacrylamide. The hydrodynamic particle diameter of the obtained amine-containing gel particles in a dispersed state in water at 30°C was about 200 nm in a nitrogen atmosphere and about 400 nm in the presence of 10% CO2.

[0069] (Synthesis Example 3) Except for changing the surfactant concentration to 0.16 mM, amine-containing gel particles were obtained in the same manner as in Synthesis Example 2. The hydrodynamic particle size of the obtained amine-containing gel particles in a dispersed state in water at 30° C. was 600 nm.

[0070] (Synthesis Example 4) A monomer solution was obtained in the same manner as in Synthesis Example 2, except that the composition of the three types of monomers was changed to 5 mol% N-[(3-dimethylamino)propyl]methacrylamide, 93 mol% N-isopropylacrylamide, and 2 mol% N,N'-methylenebisacrylamide, and the total monomer concentration was 1040 mM. After passing nitrogen gas through 2.4 mL of this solution for 10 minutes, an aqueous solution of the initiator 2,2'-azobis(2-methylpropionamidine)dihydrochloride was mixed and introduced into the bottom of a stainless steel reactor for absorbing carbon dioxide. A silicone rubber spacer (thickness 100 μm) and mold were placed in the reactor, and a glass plate was placed on top of the spacer in such a way that the monomer solution was sandwiched between them, so that the monomer solution became a liquid film with a thickness of 100 μm. In this state, the mixture was heated to 70°C and polymerized for 2 hours. After 2 hours, the glass plate and spacer were removed, and a hydrogel film in which the amine-containing gel particles were crosslinked was obtained in a state of adhering to the bottom of the stainless steel reactor. The primary diameter of the gel particles in the obtained hydrogel film was observed using a scanning electron microscope after drying. It was confirmed that the primary particle diameter of the particles was several tens to several micrometers and that cross-linked structures were formed between the particles.

[0071] [II] Synthesis of stabilizers A polymeric compound having an amino group, which serves as a stabilizer, was synthesized as follows.

[0072] (Synthesis Example 5) Synthesis of polyvinylamine 5.0 g of N-vinylformamide (NVF) purified by distillation was added to 44 mL of pure water, and nitrogen was bubbled for 30 minutes while stirring in a 60 °C oil bath. After that, 1.0 mL of an aqueous solution (19 mg / mL) of the initiator 2,2'-azobis [2- (2-imidazolin-2-yl) propane] dihydrochloride (VA-044) [manufactured by Wako Pure Chemical Industries, Ltd.] was added to this solution, and the reaction was carried out for 24 hours under a nitrogen atmosphere. Acetone was added to the solution after the reaction to precipitate the polymer, and the supernatant was removed. The resulting precipitate was dissolved in a solvent in which pure water and ethanol were mixed in a volume ratio of 3:1. Furthermore, the unreacted monomer was removed by repeating the process of precipitating the polymer with acetone, removing the supernatant, and dissolving it in an aqueous solvent several times. The solution of the resulting precipitate was concentrated under reduced pressure using an evaporator, and then vacuum dried to obtain solid poly (NVF). The dried solid was dissolved in a 2N aqueous sodium hydroxide solution so that the polymer concentration was 2% by mass, and the solution was stirred in an oil bath at 80°C for 24 hours to obtain a transparent, viscous liquid. Hydrochloric acid was added to this liquid to make the hydrochloride salt, and excess hydrochloric acid was removed using an evaporator. The liquid was dialyzed for three days using a dialysis membrane (MWCO 12-14,000, width: 75 mm, vol / length: 18 mL / mL) [manufactured by Spectrum Laboratories], and the amount of solution in the dialysis membrane was measured. The entire amount was then freeze-dried to obtain poly(vinylamine) hydrochloride (PVAm HCl). The progress of the reactions at each stage was 1 The reaction was confirmed by HNMR (DO). The counter anion was removed from this PVAm·HCl using a strongly basic ion exchange resin to obtain polyvinylamine.

[0073] (Synthesis Example 6) Synthesis of hydrophobized polyvinylamine To give the PVAm·HCl synthesized in Synthesis Example 5 temperature responsiveness, a carboxylic acid having a bulky hydrophobic site was condensed. Two types of carboxylic acid, isobutyric acid [Sigma-Aldrich] and pivalic acid [Wako Pure Chemical Industries], each having an isopropyl group or a tert-butyl group, were used. The product condensed with isobutyric acid is referred to as Isobutyl PVAm, and the product condensed with pivalic acid is referred to as PivalPVAm. Specifically, hydrophobized polyvinylamine was obtained by the following process. 100 mg (1.25 mmol amine) of PVAm·HCl was dissolved in 20 mL of MilliQ water. Triethylamine (TEA) and isobutyric acid or pivalic acid were added to this solution. At room temperature, pivalic acid is a solid, so it was dissolved in 100 L of methanol and added. After stirring for 10 minutes, the condensation agent 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) [TCI] or 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride n-hydrate (DMT-MM) [Wako Pure Chemical Industries, Ltd.] was added and stirred for 6 hours. After the reaction was completed, the reaction solution was dialyzed for 3 days using a dialysis membrane (MWCO12-14,000, width: 45 mL, vol / length: 6.42 mL / cm) [Thermo Fisher Scientific Co., Ltd.]. The condensation rate was 1 The reaction mixture after dialysis was treated with a strongly basic ion exchange resin to remove the counter anion, thereby obtaining a hydrophobic polyvinylamine.

[0074] [Evaluation of gas absorbing materials] Here, the amine-containing gel particles synthesized in Synthesis Examples 2 to 4 were used as the gel particles. (1) Study on the phase transition of amine-containing gel particles The amine-containing gel particles synthesized in Synthesis Example 2 were dissolved in water to prepare a particle solution (4 mg / mL). FIG. 4 shows the results of the temperature-dependent particle size change of the amine-containing gel particles when the particle solution was heated under conditions in which carbon dioxide was present or absent. FIG. 5 shows the change in solution pH when the particle solution was cooled to 20°C again after absorbing carbon dioxide into the particle solution at 20°C and heating it to around 60°C to dissipate carbon dioxide. FIG. 6 shows the results of a titration test using hydrochloric acid when the particle solution was held at 30°C, 45°C, 60°C, and 75°C, respectively, and FIG. 7 shows the time-dependent change in the amount of carbon dioxide dissipated when the particle solution was heated to around 75°C to dissipate carbon dioxide after absorbing carbon dioxide gas into the particle solution at 30°C. Here, when performing the measurements in FIG. 5 and FIG. 7, the absorption of carbon dioxide gas into the particle solution was performed by immersing the stainless steel reactor into which the particle solution was injected in a water tank at 20°C or 30°C and passing a mixture of carbon dioxide gas and nitrogen gas (10:90) into the container for 240 minutes. Carbon dioxide gas emission was performed by immersing the stainless steel reactor in a water bath at 60°C or 75°C. The amount of carbon dioxide emitted was determined by measuring the increase or decrease in carbon dioxide in the gas passing through the reactor during the emission process. Figure 7 also shows the results of an investigation of the amount of carbon dioxide gas emitted under similar conditions for homopolymers of N-[(3-dimethylamino)propyl]methacrylamide (a low molecular weight amine) and N-(dimethylaminopropyl)acrylamide.

[0075] As shown in Figures 4 and 5, the particle size and pH of the amine-containing gel particles change depending on the temperature. Also, from Figure 6, the apparent pKa of the particle solution was about 8 at 30°C and about 5.5 at 75°C. From these, it was confirmed that the amine-containing gel particles are temperature-responsive particles that undergo a phase transition in response to a temperature change. Also, from Figure 7, it was confirmed that the amine-containing gel particles efficiently dissipate the absorbed carbon dioxide gas by heating to 75°C. In addition, since almost no carbon dioxide emission was observed in the aqueous solution of a low molecular weight amine having a similar structure or a homopolymer polymer of N-(dimethylaminopropyl)acrylamide that does not form particles, it was suggested that the phase transition of the particles was the trigger for efficient carbon dioxide emission in the amine-containing gel particles.

[0076] (2) Comparison of gas absorption and desorption characteristics between gel particle membranes and homogeneous gel membranes Example 1 The aqueous solutions of amine-containing gel particles obtained in Synthesis Examples 2 to 4 were dried by freeze-drying to prepare methanol solutions (10 mg / mL). The methanol solutions were poured into a stainless steel container, dried at 80°C, and then water was added to cause swelling, producing gel particle films of various thicknesses. The thickness of the gel particle film was adjusted by changing the amount of methanol solution poured into the container.

[0077] Comparative Example 1 An ethanol solution of monomers with the same composition as that prepared in Synthesis Example 2 was poured into a stainless steel vessel, degassed for 30 minutes under a nitrogen atmosphere, and then a DMF solution of benzoyl peroxide was added. A polymer membrane was produced by reacting for 6 hours or more at room temperature under a nitrogen atmosphere. This polymer membrane was washed with water, dried at 80°C, and swelled by pouring water into it to obtain various gel homogeneous membranes with different thicknesses. The thickness of the gel homogeneous membrane was adjusted by changing the amount of monomer solution poured into the vessel. Here, the term "gel homogeneous membrane" refers to a dense film-like membrane that does not contain particles.

[0078] The reactor in which the gel particle film was formed in Example 1 and the reactor in which the gel homogeneous film was formed in Comparative Example 1 were immersed in a water bath at 30°C, and a carbon dioxide-containing gas obtained by humidifying a mixed gas of carbon dioxide gas and nitrogen gas (10:90) with a humidifier at 60°C was passed through these containers at 300mL / min for about 10 minutes, and after confirming with an infrared carbon dioxide concentration meter that the absorption of carbon dioxide into the film had been completed, the containers were transferred to a water bath at 75°C and held there for 3 minutes. During this time, the amount of carbon dioxide in the gas passing through the container was quantified with an infrared carbon dioxide concentration meter, and the carbon dioxide emission rate and absorption rate were calculated from the increase or decrease in the amount of carbon dioxide. The results of measuring the carbon dioxide gas emission rate for the gel particle film of Example 1 and the gel homogeneous film of Comparative Example 1 are shown in Figures 8 and 9, and the results of measuring the carbon dioxide absorption rate are shown in Figure 10. The numerical values ​​in units of "nm" shown in Figures 8 to 10 are the particle diameters of the gel particles, "300 nm gel particle film" represents the film of the gel particles synthesized in Synthesis Example 2, "1 μm gel particle film" represents the film of the gel particles synthesized in Synthesis Example 3, and "crosslinked gel particle film" represents the film of the gel particles synthesized in Synthesis Example 4. As shown in Figures 8 to 10, all of the gel particle films have a larger amount of carbon dioxide absorption and emission than the gel homogeneous film, and it was confirmed that the carbon dioxide absorption and emission capacity is improved by forming the polymer compound having an amino group into a particulate form. The reason why the carbon dioxide diffusion rate of the gel particle membrane is particularly faster than the absorption rate is presumably because, in the carbon dioxide absorption process, the gel particles swell significantly and the gaps between the particles are small, whereas in the diffusion process, the gel particles shrink and the gaps that contribute to gas diffusion are large.

[0079] [Evaluation of gas absorbers] In the evaluation of the gas absorbent, the amine-containing gel particles synthesized in Synthesis Example 1 were used as the gel particles. (3) Effect of supporting gel particle membranes using various thin plates as supports As supports, a stainless steel thin plate with a thickness of 0.1 mm or 0.3 mm (thermal conductivity is about 16 W / (m·K)), a thin iron plate with a thickness of 0.1 mm (thermal conductivity is about 80 W / (m·K)), and a graphite sheet with a thickness of 0.1 mm (Panasonic, PGS graphite sheet EYGS182310, thermal conductivity is 600-800 W / (mK)) were prepared, and a silicone rubber sheet with holes was attached to these supports as a mold. On the other hand, the amine-containing dry gel particles synthesized in Synthesis Example 1 were dissolved in methanol to prepare a particle solution (50 mg / 3 mL). This particle solution was applied to the inside of the mold of the above-mentioned support and placed in an incubator at 40 ° C. and dried under reduced pressure. The particle solution was similarly applied to the back side of the support and dried in a dryer at 80 ° C. for 30 minutes to obtain a laminate consisting of the support and the dry particle film. However, since the silicone rubber sheet of the mold does not adhere to the graphite sheet, the silicone rubber sheet was fixed with a clip and used, and the particle solution was spread with a brush while being heated on a hot plate at 80 ° C. to support the carrier. Thereafter, like the other carriers, the carrier coated with the particle solution was dried in a dryer at 80 ° C. to obtain a laminate. After the weight of the dried laminate was measured, the weight of the supported amine-containing dry gel particles was quantified, and the amine-containing dry gel particles were gelled by adding 4 equivalents (4 mL / g) of water. Through the above process, a gas absorber in which a gel particle film was supported on a carrier was obtained. The thickness of the gel particle film of each obtained gas absorber was 37 μm.

[0080] Next, a reactor shown in Fig. 11 was prepared. This reactor has a pair of acrylic plates 1, butyl rubber gaskets 2 arranged on the opposing surfaces of the pair of acrylic plates 1, and a plurality of screws 4 for fixing the pair of acrylic plates 1 together, and is configured such that a gas absorber 3 is sandwiched between the pair of butyl rubber gaskets 2. In addition, a gas inlet 5 and a gas outlet 6 are provided on the upper acrylic plate 1 of this reactor, and gas from a gas supply means (not shown) is supplied to the gas absorber 3 through the gas inlet 5 and then discharged to the outside through the gas outlet 6. In this experimental example, a gas absorber was fixed to the reactor shown in FIG. 11, and a carbon dioxide absorption and desorption experiment was performed by passing a carbon dioxide-containing gas through it (10 mL / min). The carbon dioxide-containing gas was 60°C gas obtained by humidifying nitrogen gas containing 10% carbon dioxide with a humidifier at 60°C. Carbon dioxide absorption was performed by placing the reactor in a water tank at 30°C, and carbon dioxide desorption was performed by placing the reactor in a water tank at 75°C. The amount of carbon dioxide emitted and absorbed by the gas absorber was calculated from the increase and decrease in carbon dioxide in the gas passing through the reactor. The change over time in the amount of carbon dioxide absorbed and emitted by each gas absorber is shown in FIG. 12 and FIG. 13. In FIG. 12 and FIG. 13, "sus" indicates that the carrier is a stainless steel thin plate, "Fe" indicates that the carrier is an iron thin plate, and "C" indicates that the carrier is a graphite sheet. In FIG. 12, the reactor was placed in a 75°C water bath at 0 and 75 minutes from the start of the experiment to measure the amount of carbon dioxide emitted, and was placed in a 30°C water bath at 25 and 100 minutes from the start of the experiment to measure the amount of carbon dioxide absorbed. In FIG. 12, the amount of emission and the amount of absorption of the gas absorber from the time points of 0, 25, 75, and 100 minutes are graphed. In FIG. 13, the reactor was placed in a 75°C water bath at 0, 75, and 140 minutes from the start of the experiment to measure the amount of emission, and was placed in a 30°C water bath at 30, 100, and 170 minutes from the start of the experiment to measure the amount of absorption. In FIG. 13, the amount of emission and the amount of absorption of the gas absorber from the time points of 0, 30, 75, 100, 140, and 170 minutes are graphed. The vertical axis of the graphs in FIG. 12 and FIG. 13 represents the amount of carbon dioxide emitted per mass of the amine-containing dry gel particles of the gas absorber, and a negative amount of emission indicates that carbon dioxide is being absorbed.

[0081] When a 0.1 mm-thick stainless steel thin plate (thermal conductivity is about 16 W / (m K)) was used as the carrier, it took about 14 minutes to emit 25 mL of carbon dioxide per 1 g of amine-containing dry gel particles, and about 26 minutes to absorb 25 mL of carbon dioxide, and the maximum reversible carbon dioxide emission / absorption amount per 1 g of amine-containing dry gel particles was 31-38 mL (Figs. 12 and 13). On the other hand, when the stainless steel thin plate was made 0.3 mm thick, the emission rate was accelerated by about 1.5 times and the absorption rate was accelerated by about 2 times compared to the case of a 0.1 mm-thick stainless steel thin plate, and it took only about 10 minutes to emit 25 mL of carbon dioxide per 1 g of amine-containing dry gel particles, and about 13 minutes to absorb 25 mL of carbon dioxide per 1 g of amine-containing dry gel particles (Fig. 12). Similarly, the reversible carbon dioxide emission / absorption amount per 1 g of amine-containing dry gel particles was improved to 42-48 mL (Fig. 12). On the other hand, when a thin plate of iron, which has a relatively high thermal conductivity (thermal conductivity is about 80 W / (m K)), was used as the carrier, the emission rate was accelerated by about 1.8 times and the absorption rate by about 2.2 times, even though the plate was the same 0.1 mm thick. It took only about 8 minutes to emit 25 mL of carbon dioxide per 1 g of amine-containing dry gel particles, and only about 12 minutes to absorb 25 mL of carbon dioxide. Similarly, the reversible carbon dioxide emission and absorption amount per 1 g of amine-containing dry gel particles was 33 to 42 mL (Figure 13). In addition, when a 0.1 mm thick graphite sheet (Panasonic, PGS graphite sheet EYGS182310, thermal conductivity 600-800 W / (mK)) was used, the emission rate and absorption rate were both accelerated by about 2.3 times compared to when a 0.1 mm thick stainless steel thin plate was used, and it took only about 6 minutes to emit 25 mL of carbon dioxide per 1 g of amine-containing dry gel particles, and about 10 minutes to absorb 25 mL of carbon dioxide per 1 g of amine-containing dry gel particles. Similarly, the reversible carbon dioxide emission and absorption amount per 1 g of amine-containing dry gel particles was improved to 60 mL (Figure 13). Similarly, when a 0.1 mm thick aluminum thin plate was used, the emission rate was accelerated by about 1.8 times, and the absorption rate was accelerated by about 1.5 times, compared to when a 0.1 mm thick stainless steel thin plate was used.

[0082] (4) Effect of supporting various amounts of amine-containing gel particle membranes A graphite sheet with a thickness of 0.1 mm (Panasonic, PGS graphite sheet EYGS182310, thermal conductivity 600-800 W / (mK)) was used as a carrier, and the thickness of the amine-containing gel particle film was changed from 37 μm to 230 μm. As a result, the reversible carbon dioxide absorption amount per reactor internal volume improved from 208 mL / L to 1160 mL / L (FIG. 14). In FIG. 14, carbon dioxide was sufficiently absorbed at 30°C to reach equilibrium, and then the temperature was raised to 75°C to dissipate carbon dioxide. The start of dissipation was set to 0 minutes, and carbon dioxide was dissipated. Then, 30 minutes after the start of the experiment, the reactor was placed in a water bath at 30°C to measure the amount of carbon dioxide absorbed. FIG. 14 is a graph of the amount of carbon dioxide emitted and absorbed by the gas absorber from 0 minutes and 30 minutes, and the vertical axis of the graph represents the amount of carbon dioxide emitted per reactor internal volume. A negative absorption rate indicates that carbon dioxide is being absorbed.

[0083] (5) Effect of supporting the accelerator-containing amine-containing gel particle membrane A 0.1 mm thick graphite sheet (Panasonic, PGS graphite sheet EYGS182310, thermal conductivity 600-800 W / (mK)) was used as a support to support a 230 μm amine-containing gel particle film, and 1 M N,N',N"-pentamethyldiethylenetriamines was added as a promoter. As a result, the reversible carbon dioxide absorption per reactor volume increased from 1160 mL / L to 4000 mL / L.

[0084] (6) Effect of supporting thin gel film using various fibers as carriers FIG. 15 shows the stainless steel reactor used in this experiment. 3 The reactor has a space 11 having a volume of (length 80 mm, width 150 mm, depth 5 mm), and 13 flow straightening plates 12 are arranged at 10 mm intervals within the space 11. The reactor is also provided with a gas inlet 13 for introducing gas from a gas supply means (not shown) into the space 11, and a gas outlet 14 for discharging gas from the space 11.

[0085] A predetermined amount of amine-containing dry gel particles was dissolved in methanol and stirred overnight. The concentration of the solution was adjusted to about 17 mg / mL. Next, stainless steel fiber felt (Nippon Seisen Co., Ltd., Naslon Felt 12-5-1500 and 8-5-1500, fiber diameter 12 μm and 8 μm, thickness 5 mm, basis weight 1500 g / m) cut to 80 mm × 8 mm × 5 mm was used as a carrier. 2) and aluminum fiber felt (fiber diameter 100 μm) were prepared. These carriers were fixed in the space 11 of the reactor shown in FIG. 15, placed on a hot plate at 80° C. and heated. A methanol solution of amine-containing dry gel particles was evenly applied to the heated carrier with a syringe. When the evaporation of methanol was slow when heated from below, heat was applied from above using a dryer to evaporate the methanol so that the amine-containing dry gel particles could be uniformly supported. A predetermined amount of water was added to the amine-containing dry gel particles supported on the carrier to gel them, and an amine-containing gel support material (gas absorber) was prepared. This gas absorber was placed inside the reactor shown in FIG. 15, and a carbon dioxide absorption and desorption experiment was performed by passing a carbon dioxide-containing gas through it (10 mL / min). As the carbon dioxide-containing gas, nitrogen gas containing 10% carbon dioxide was used, which was humidified with a 60° C. humidifier. Carbon dioxide absorption was performed by placing the reactor in a water tank at 30° C., and carbon dioxide desorption was performed by placing the reactor in a water tank at 75° C. The gas passing through the reactor was passed through a condenser at 5°C to remove moisture from the gas, and the amount of carbon dioxide in the gas was quantified at regular intervals using gas chromatography (Shimadzu Corporation, product name GC-TCD). The amount of carbon dioxide emitted and absorbed by the gas absorbent was calculated from the increase or decrease in the amount of carbon dioxide in the gas. Figures 16 to 23 show the change over time in the amount of carbon dioxide absorbed and emitted by each gas absorbent. Figures 16 to 19 are graphs of gas absorbents whose carrier is Naslon felt 12-5-1500. In Figures 20 to 23, "AlΦ100" indicates that the carrier is aluminum fiber felt, "susΦ12" or "12-5-1500" indicates that the carrier is Naslon felt 12-5-1500, and "8-5-1500" indicates that the carrier is Naslon felt 8-5-1500. In Figures 16 to 23, the numerical values ​​in units of "mg / ml" represent the amount of amine-containing dry gel particles applied to the carrier. In Figures 16 to 23, the reactor was placed in a 75°C water bath at 0, 71, and 142 minutes from the start of the experiment to measure the amount of carbon dioxide emitted, and was placed in a 30°C water bath at 25 and 96 minutes from the start of the experiment to measure the amount of carbon dioxide absorbed. In Figures 16 to 23, the amounts emitted or absorbed by the gas absorber are graphed from 0, 25, 71, 96, and 142 minutes.16 to 23, the vertical axis of the graphs in FIGS. 16, 18, 20, and 22 represents the amount of carbon dioxide emitted per volume of fiber assembly, and the values ​​represented by the vertical axis of the other graphs are the same as the values ​​represented by the vertical axis of FIG.

[0086] When fibers are used as a carrier, it was found that the thickness of the fibers and the amount of gel carried by them affect the reversible absorption amount and absorption speed. 2 When various amounts of amine-containing gel particles (water addition amount 4mL / g) were applied to the amine-containing dry gel, the reversible carbon dioxide absorption amount was increased by about 2 times when the amount of applied amine-containing dry gel particles was increased from 100mg to 200mg, but when it was increased from 200mg to 400mg, the reversible carbon dioxide absorption amount was dramatically decreased (Figures 16 and 17). In addition, when the amount of added water was changed while keeping the amount of amine-containing dry gel particles constant, the reversible carbon dioxide absorption amount was slightly improved when the amount of added water was reduced from 4mL / g to 2mL / g, even if the amount of amine-containing dry gel particles was large (Figures 18 and 19). From the above results, it was found that it is necessary to limit the gel packing rate including water to about 15-40% for efficient reversible absorption of carbon dioxide. When the fiber diameter was changed from 12μm to 100μm (aluminum fiber) at the optimized packing rate, the reversible carbon dioxide absorption performance decreased despite the high thermal conductivity of the material (aluminum) (Figures 20 and 21). This is thought to be because the surface area of ​​the fiber decreases as the fiber diameter increases, and the thickness of the gel particle film increases. On the other hand, when the fiber diameter was changed from 12 μm to 8 μm, it was found that the diffusion and absorption behavior hardly changed (Figures 22 and 23). This shows that if fibers thinner than 100 μm are used, the absorption and diffusion performance does not depend so strongly on the fiber diameter, and high performance can be demonstrated.

[0087] (7) Comparison of results with and without gel particle membranes supported on the carrier (Example of preparation and evaluation of gel particle membrane not supported on a carrier) 2.4 g of amine-containing dry gel particles were dissolved in methanol and stirred overnight to obtain a methanol solution of amine-containing dry gel particles (particle solution). The above-mentioned stainless steel reactor (Figure 15) was placed on a hot plate at 80 °C and heated, and the prepared particle solution was applied to the inner surface of the reactor while evaporating the methanol. Specifically, one-third of the total solution was applied to the lower part of the stainless steel reactor, one-third of the total solution to the upper lid part, and one-third of the total solution to the comb part of the lid. After drying the particle solution, 4.8 mL of water was added to turn the film into a gel film, and an amine-containing gel particle film was formed on the inner surface of the reactor. Carbon dioxide absorption and desorption experiments were carried out by passing a carbon dioxide-containing gas through the reactor (50 mL / min). The carbon dioxide-containing gas was 60°C gas obtained by humidifying nitrogen gas containing 10% carbon dioxide with a humidifier at 60°C. Carbon dioxide absorption was carried out by placing the reactor in a water tank at 30°C, and carbon dioxide desorption was carried out by placing the reactor in a water tank at 75°C. The gas passing through the reactor was passed through a condenser at 5°C to remove moisture from the gas, and the amount of carbon dioxide in the gas was quantified at regular intervals using gas chromatography (manufactured by Shimadzu Corporation, product name GC-TCD). The amount of carbon dioxide absorbed and released by the gel particle film was calculated from the increase and decrease in the amount of carbon dioxide in the gas. Figure 24 shows the change over time in the amount of carbon dioxide absorbed and released by the gel particle film.

[0088] (Example of preparation and evaluation of gel particle membrane supported on a carrier) 2.4 g of the amine-containing dry gel particles were dissolved in methanol and stirred overnight to obtain a methanol solution of the amine-containing gel particles (particle solution). A stainless steel fiber felt (Naslon felt, 12-5-1500 / m 2) was filled, and the reactor was placed on a hot plate at 80 ° C. and heated. The particle solution was evenly applied using a syringe so that 200 mg of amine-containing dry gel particles were supported on each felt in the reactor, and the particle solution was left in this state to evaporate the methanol. If the evaporation of methanol was slow, heat was applied from above using a dryer to evaporate the methanol so that the amine-containing dry gel particles were uniformly supported. 400 μL (4.8 mL in total) of water was added to each of the 12 supports supporting the amine-containing dry gel particles to gel the particles, and a gas absorber with an amine-containing gel particle film supported on the support was obtained. Carbon dioxide absorption and desorption experiments were conducted by passing a carbon dioxide-containing gas (50 mL / min) through a container in which a gas absorber was formed. The carbon dioxide-containing gas was 60°C gas obtained by humidifying nitrogen gas containing 10% carbon dioxide with a humidifier at 60°C. Carbon dioxide absorption was performed by placing the reactor in a water tank at 30°C, and carbon dioxide desorption was performed by placing the reactor in a water tank at 75°C. The gas passing through the reactor was passed through a condenser at 5°C to remove moisture from the gas, and the amount of carbon dioxide in the gas was quantified at regular intervals using gas chromatography (Shimadzu Corporation, product name GC-TCD). The amount of carbon dioxide absorbed and released by the gas absorber was calculated from the increase and decrease in carbon dioxide in the gas. Figure 24 shows the change over time in the amount of carbon dioxide absorbed and released in each absorber. In FIG. 24, "12-5-1500 felt" represents a gas absorbent using stainless steel fiber felt (Naslon felt 12-5-1500) as a carrier, and the numerical value in "mg / ml" represents the amount of amine-containing dry gel particles applied to the carrier or container. In FIG. 24, the reactor was placed in a water bath at 30°C at 25, 96, and 167 minutes after the start of the initial emission to measure the amount of carbon dioxide absorbed, and was placed in a water bath at 75°C at 0, 71, and 142 minutes after the start of the experiment to measure the amount of carbon dioxide emitted. In FIG. 24, the amount of emission or absorption of the gas absorbent from the time points of 0, 25, 71, 96, 142, and 167 minutes is graphed. The numerical values ​​represented on the vertical axis of the graph in FIG. 24 are the same as those represented on the vertical axis of FIG. 12.

[0089] As a result of the above experiments, the gel particle film formed directly inside the reactor was only able to reversibly absorb 50-120mL of carbon dioxide, while the gas absorber in which the gel particle film was supported by filling a felt made of stainless steel fibers with a fiber diameter of 12μm inside the same reactor was able to reversibly absorb 98-130mL of carbon dioxide. In addition, when the gel particle film was formed directly inside the reactor, it took 23 minutes to dissipate 120mL of carbon dioxide gas in the above reversible absorption process, whereas when the gel particle film was supported on the stainless steel fiber felt, the dissipation of carbon dioxide gas was completed within 9 minutes. Similarly, when the gel particle film formed directly inside the reactor was used, it took 45 minutes to absorb about 120mL of carbon dioxide gas in the above reversible absorption process, whereas when the gel film was supported on the stainless steel fiber felt, it was able to absorb 120mL of carbon dioxide gas within 18 minutes. As described above, it was confirmed that by using metal fibers as a carrier and supporting a gel particle membrane at an appropriate filling rate, the average reversible absorption amount can be improved by 1.3 times, the diffusion rate by 2.6 times, and the absorption rate by 2.5 times.

[0090] Next, experiments were carried out using felt made of stainless steel fibers and sintered metal fibers made by sintering felt made of stainless steel fibers. On an iron plate heated to 80℃, a felt made of stainless steel fibers (Naslon felt, 12-5-1500 / m 2 ) or sintered metal fiber (Nippon Seisen, SUS316L, basis weight 1600g / m) 2, fiber diameter 50μm, porosity 89%) was placed on the substrate, and 550μL of a solution in which the amine-containing gel particles obtained in Synthesis Example 1 were dissolved in methanol to a concentration of 20mg / mL was added, followed by drying. After that, the substrate was placed in a reactor, and 4 equivalents of water were added to the amine-containing gel particles. In each experiment, three samples were prepared with different gel particle packing rates, and the carbon dioxide emission and absorption amounts were measured for each sample by the same method as above. Figure 25 is a graph showing the relationship between the gel packing rate and the carbon dioxide emission and absorption amounts. From Figure 25, it was confirmed that when sintered metal fibers were used, the high carbon dioxide absorption and desorption ability of the gel particles could be maintained even when the gel particle packing rate was high (for example, 60% or more). Next, carbon dioxide absorption and desorption experiments were carried out in the same manner as above using sintered metal fibers (fiber diameters 12 μm and 50 μm) made by sintering stainless steel fiber felt, foamed metal (Sumitomo Metal, Celmet #4, #5, and #7), and sintered nickel fibers (fiber diameter 40 μm). In Fig. 26, the reactor was placed in a water bath at 30°C 25 and 96 minutes after the start of the initial desorption to measure the amount of carbon dioxide absorbed, and was placed in a water bath at 75°C 0 and 71 minutes after the start of the experiment to measure the amount of carbon dioxide emitted. In Fig. 26, the amount of emission or absorption of the gas absorber from 0, 25, 71, and 96 minutes is graphed. The values ​​on the vertical axis of the graph in Fig. 26 are the same as those on the vertical axis of Fig. 12. Fig. 26 shows that foamed metal can be used in an equivalent manner to sintered metal fibers. It was also confirmed that sintered nickel fiber is excellent in terms of the absorption rate, absorption amount, and emission amount and rate of carbon dioxide, and can be preferably used.

[0091] When 2.4 g of amine-containing dry gel particles were dissolved in methanol and uniformly applied inside the reactor shown in Figure 15, and then dried, 4.8 mL of water was added to create a gel particle film. Only 50 to 120 mL of carbon dioxide could be reversibly absorbed, but the volume of the film was approximately the same as that of the reactor, about 60,000 mm. 3Four graphite sheets (Panasonic, PGS graphite sheet EYGS182310, thermal conductivity 600-800W / (mK)) with a thickness of 0.1 mm were stacked inside a space (length 40 mm, width 170 mm, depth approximately 8.8 mm) and each sheet was placed on both sides (6800 mm 2 When 2.4 grams of gel particles were uniformly applied to a substrate (40 mm long, 170 mm wide) and 4.8 mL of water was added to form a gel film, 120 to 140 mL of carbon dioxide could be reversibly absorbed. In addition, when a gel particle film was directly formed inside the reactor, it took 23 minutes to dissipate 120 mL of carbon dioxide gas in the above-mentioned reversible absorption process, whereas when four graphite sheets carrying a gel film were stacked, the dissipation of carbon dioxide gas could be completed within 15 minutes. Similarly, when a gel particle film was directly formed inside the reactor, it took 45 minutes to dissipate about 20 mL of carbon dioxide gas in the above-mentioned reversible absorption process, whereas when four graphite sheets carrying a gel film were stacked, the dissipation of carbon dioxide gas could be completed within 25 minutes. As described above, by supporting a gel particle film on the graphite sheet carrier, the average reversible absorption amount was improved by 1.5 times, the diffusion rate by 1.5 times, and the absorption rate by 1.8 times. In addition, when 2.4 g of amine-containing dry gel particles were dissolved in methanol and uniformly applied inside the reactor shown in Figure 15, and then dried, 4.8 mL of water was added to create a gel particle film. Only 50 to 120 mL of carbon dioxide could be reversibly absorbed, but the gas flow path had a volume of approximately 60,000 mm, which is almost the same as that of the conventional reactor. 3 The heat transfer surface of six stainless steel thin plates (each 18,000 mm2) of a plate heat exchanger (HISAKA WORKS, LTD., UX-0005A-J-8 plates) with a length of 40 mm, width of 170 mm, and depth of approximately 8.8 mm 2) was uniformly coated with 2.4 grams of amine-containing dry gel particles dissolved in methanol, dried, and then 4.8 mL of water was added to support a gel particle film. In addition, when the gel particle film was directly formed inside the reactor, 23 minutes were required to dissipate 120 mL of carbon dioxide gas in the above-mentioned reversible absorption process, whereas when four stainless steel thin plates carrying the gel film were stacked, the dissipation of carbon dioxide gas was completed within 14 minutes. Similarly, when the gel particle film was directly formed inside the reactor, 45 minutes were required to dissipate about 120 mL of carbon dioxide gas in the above-mentioned reversible absorption process, whereas when four stainless steel thin plates carrying the gel film were stacked, the dissipation of carbon dioxide gas was completed within 24 minutes. As described above, by supporting a gel particle film on the stainless steel thin plate carrier, the average reversible absorption amount was improved by 1.5 times, the diffusion rate by 1.6 times, and the absorption rate by 1.9 times.

[0092] In addition, the heat transfer surface of six stainless steel thin plates (each 18,000 mm 2 ) 3.9 grams of the amine-containing dry gel particles obtained in Synthesis Example 1 were dissolved in methanol and uniformly applied to the substrate, dried, and 4.8 mL of water was added to support the gel particle film. Nitrogen gas containing 10.9% CO2 was passed through at 200 mL / min to perform carbon dioxide emission and absorption. The reactor was placed in a water bath at 30°C at 25 minutes, 96 minutes, and 167 minutes after the start of the initial emission to measure the amount of carbon dioxide absorbed, and the reactor was placed in a water bath at 75°C at 0 minutes, 71 minutes, and 142 minutes after the start of the experiment to measure the amount of carbon dioxide emitted. In FIG. 27, the amount of emission or absorption of the gas absorber from the time points of 0 minutes, 25 minutes, 71 minutes, 96 minutes, 142 minutes, and 167 minutes is graphed. The values ​​represented by the vertical axis of the graph in FIG. 27 are the same as the values ​​represented by the vertical axis of FIG. 12. Extremely good results were obtained for the absorption rate, absorption amount, emission amount, and emission rate of carbon dioxide. Figure 28 shows the change in vapor pressure when the temperature of the water bath is changed between 30 and 75° C. The results in Figure 28 indicate that the gel particle film reversibly absorbs water vapor as well as carbon dioxide.

[0093] (8) Study of methods for stabilizing gel-like films Gel particle membranes consisting only of amine-containing gel particles have high water absorption, and depending on the conditions of repeated use, the membrane thickness may increase, leading to blockage of the gas flow path, which may result in a decrease in the gas absorption / emission rate and reversible absorption amount. Furthermore, the gel particle membrane may become fluidized and flow out from the carrier surface. To solve these problems, we added a stabilizer to the gel particle membrane and investigated the conditions under which a stable membrane can be obtained even under conditions of a large amount of water added.

[0094] (8-1) Stabilization of amine-containing gel particle membranes using polyvinyl alcohol / polyethylene copolymer as a stabilizer Polyvinyl alcohol / polyethylene copolymer was added as a stabilizer to the amine-containing gel particle membrane consisting of amine-containing gel particles at 33 mass% or 50 mass% (mass fraction of solids excluding dispersion medium), and the behavior of the gel particles was observed when an excess amount of water was added. First, a particle solution of amine-containing dry gel particles labeled with a fluorescent dye (dansyl group), unlabeled amine-containing dry gel particles, and a stabilizer, polyvinyl alcohol / polyethylene copolymer, was dissolved in a solvent, and the coating amount of the dry gel particles was 113 mg / m. 2The gel particle film was formed by applying the solution to the inside of a glass vial so that the solution was 100% by weight and drying it in an oven at 80°C for 1.5 hours. The polyvinyl alcohol / polyethylene copolymer used was EVOH (E29) (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., polyethylene copolymerization ratio: 29%) or EVOH (E44) (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., polyethylene copolymerization ratio: 44%). A gel particle film was formed in a glass vial in the same manner except that no stabilizer was used. An excess amount of water (10 mL / 20 mg polymer) was poured into each glass vial and left for 48 hours, and the amount of amine-containing gel particles dissolved from the gel particle film into the water layer was calculated from the amount of fluorescent dye. As a result, the amine-containing gel particle film without the addition of a stabilizer was completely dissolved, and strong fluorescence above the detection limit was observed. When polyvinyl alcohol / polyethylene copolymer (EVOH (E29)) with a polyethylene copolymerization ratio of 29% was used as a stabilizer, the amount of amine-containing gel particle film dissolved was reduced to less than half by adding 33 mass% compared to when no stabilizer was added. The gel particle film to which the stabilizer was added at 50% by mass almost completely suppressed the elution, and the amount of fluorescent dye-labeled amine-containing gel particles eluted in the water was below the detection limit. On the other hand, in the case of a stabilizer (EVOH (E44)) with a polyethylene polymerization ratio of 44%, the amount of fluorescent dye dissolved in the water layer was suppressed below the detection limit by adding 33% or 50% by mass. From the above, it was found that adding a polymer with a high polyethylene content and high crystallinity as a stabilizer is effective in suppressing the elution of amine-containing gel particles at room temperature. Furthermore, the amount of carbon dioxide absorbed and released by the gel particle film created under the same conditions was measured using the reactor in Figure 15. The change over time in the amount of carbon dioxide released by the gel particle film is shown in Figure 29, and the change over time in the amount of carbon dioxide absorbed by the gel particle film is shown in Figure 30. In Figures 29 and 30, the vertical axis represents the amount of carbon dioxide released or absorbed per unit mass of the amine-containing dry gel particle. 29 and 30, the amount of carbon dioxide absorbed and released by the gel particle membrane with added stabilizer was equivalent to that of the gel particle membrane without added stabilizer. However, the absorption rate tended to be slightly slower when the amount of stabilizer added was increased.

[0095] As described above, it was confirmed that the addition of polyvinyl alcohol / polyethylene copolymer dramatically suppressed the dissolution of amine-containing gel particles at room temperature, but when the temperature was repeatedly changed between 75°C and 30°C in an environment where water was present and carbon dioxide was repeatedly released / absorbed, the stability of the film decreased under some conditions and the gel particle film was sometimes fragmented. Therefore, we investigated a method for creating gel particle films that would maintain their morphology more stably even in environments where the temperature and amount of carbon dioxide absorbed changed significantly. A predetermined amount of stabilizer (EVOH (E44)) and amine-containing dry gel particles were dissolved in a mixed solvent of isopropanol and water (mixed volume ratio 6:4), applied to a glass vial, and stirred at 60°C for 4 hours. A titanium-based crosslinker (TC-310 or TC-400 manufactured by Matsumoto Fine Chemical Co., Ltd.) diluted with the same solvent was added to this particle solution containing the stabilizer so that the mass ratio was about 1 / 8 of the stabilizer (EVOH (E44)), and after stirring for 1 hour, a particle film was formed by drying for 12 hours in a hot air dryer at 60°C. The particle film was then heat-treated for 1 hour at 110°C or 150°C to stabilize it. 200 equivalents of water were added to this particle film to gel it, and it was left to stand at room temperature for 12 hours. As a result, the gel particle membrane that gelled after heat treatment at 110°C was somewhat stabilized by adding 9 mass% or more (mass fraction of solids excluding dispersion medium) of stabilizer, but the membrane was observed to fragment and peel off from the glass vial (Figure 31(A)). On the other hand, the gel particle membrane that gelled after heat treatment at 150°C did not break even after being left undisturbed at room temperature for 12 hours, and it was confirmed that the membrane was sufficiently stabilized by adding 3 mass% (mass fraction of solids excluding dispersion medium) of stabilizer. In addition, the phenomenon of dissolution of the gel particle membrane was almost completely suppressed (Figure 31(B)). Furthermore, when the temperature was repeatedly changed between 75°C and 30°C in the presence of 10% carbon dioxide, swelling of the gel particle film in which a crosslinked structure was formed with a titanium crosslinker (TC-400) was observed by adding 6% and 33% of the stabilizer (mass fraction of solids excluding the dispersion medium), and swelling of the film in which a titanium-based crosslinker (TC-310) was added was observed by adding 6% of the stabilizer (mass fraction of solids excluding the dispersion medium) (Figure 31(C)). For the gel particle film in which a crosslinked structure was formed with TC-310 and 33% of the stabilizer (mass fraction of solids excluding the dispersion medium) was added, no significant change in the degree of swelling was observed even after two cycles of temperature change.Furthermore, the carbon dioxide reversible absorption performance was evaluated for a gel particle membrane in which a crosslinked structure was formed with TC-310 and 33 mass% (mass fraction of solids excluding dispersion medium) of stabilizer was added, using the reactor in Figure 15. It was confirmed that the carbon dioxide absorption and emission amounts were about 10% lower than those of a gel particle membrane without stabilizer, but there was almost no adverse effect on the emission rate and absorption rate (Figure 32). In Figure 32, "EVOH & TC-310" represents a crosslinked structure formed with TC-310 and stabilizer EVOH (E44) was added, and "No additive" represents a crosslinked structure formed with TC-310 and stabilizer EVOH (E44) was not added. In Figure 32, the reactor was placed in a 30°C water bath at 14 minutes and 74 minutes from the start of the experiment to measure the carbon dioxide absorption amount, and was placed in a 75°C water bath at 0 minutes and 60 minutes from the start of the experiment to measure the carbon dioxide emission amount. 32, the amounts of emission and absorption of the gas absorber from the time points 0, 14, 60, and 74 are graphed. The values ​​represented on the vertical axis of the graph in FIG. 32 are the same as those represented on the vertical axis in FIG.

[0096] (8-2) Stabilization of gel particle membranes using polyvinylamine as a stabilizer As a stabilizer for gel particle membrane, polyvinylamine was investigated in addition to polyvinyl alcohol / polyethylene copolymer. The aqueous solution in which the amine-containing gel particles were dissolved and the polyvinylamine aqueous solution were mixed in various mass ratios, stirred for 3 days, and then coated on a glass vial and dried under reduced pressure at 40°C, and then dried at normal pressure at 80°C for 1 hour. This resulted in the formation of an amine-containing dry gel particle film in the glass vial. Four equivalents of water were added to this amine-containing dry gel particle film to form a gel particle film, and 10% carbon dioxide-containing gas was passed through at room temperature for 3 hours to dissolve the carbon dioxide. The gel particle film was then heated to 75°C and allowed to stand for 12 hours in the presence of 10% carbon dioxide-containing gas. This was used to examine whether the primary amines of polyvinylamine were crosslinked by carbon dioxide to stabilize the film. 200 masses of water were poured into the glass vial, and the film was then allowed to stand for 1 hour, after which the stability of the film was observed. As a result, it was found that a gel particle film to which 9 mass% (mass fraction of solids excluding the dispersion medium) or more of polyvinylamine was added was relatively stable. The stability of the membrane did not improve when the membrane was left standing at room temperature in the presence of 10% carbon dioxide gas for 12 hours, instead of heating to 75°C and leaving it standing in the presence of 10% carbon dioxide gas for 12 hours. This suggests that the carbon dioxide dissolved in the membrane causes a crosslinking reaction at 75°C, stabilizing the membrane.

[0097] (8-3) Stabilization of thin films of gel particles using polymerizable compounds as stabilizers We investigated the stabilization of gel particle membranes by using a polymerizable compound as a stabilizer for the gel particle membrane and polymerizing it in the presence of a polymerization initiator. 100 mg of the amine-containing gel particles obtained in Synthesis Example 1 was dissolved in 6 mL of methanol. In addition, 95 parts by mass of N,N-dimethylaminopropyl methacrylamide (DMAPM) and 5 parts by mass of N,N'-methylenebisacrylamide (BIS) were dissolved in methanol to prepare a methanol solution with a concentration of 0.05 mg / mL. In addition, a methanol solution of a polymerization initiator (IRGACURE184) was also prepared, and these three kinds of methanol solutions were mixed. The mixing ratio was such that the total amount of DMAPM and BIS was 56 parts by mass relative to 100 parts by mass of the amine-containing gel particles. In addition, the polymerization initiator was mixed in an amount of 1 / 60 mol relative to the monomer. This mixed solution was cast into a stainless steel reactor, slowly dried at room temperature, and then dried in a thermostatic chamber at 35°C. Thereafter, it was irradiated with ultraviolet light to polymerize. Further, water was added to obtain a gel particle film having a uniform film shape. In this manufacturing method, even if a large amount of water was added, a gel particle film having a nearly uniform film shape was obtained by only partially swelling. A carbon dioxide absorption and desorption experiment was carried out in the same manner as above. In FIG. 33, the reactor was placed in a water bath at 30° C. at 25 minutes, 96 minutes, and 167 minutes after the start of the initial desorption to measure the amount of carbon dioxide absorbed, and was placed in a water bath at 75° C. at 0 minutes, 71 minutes, and 142 minutes after the start of the experiment to measure the amount of carbon dioxide emitted. In FIG. 33, the amount of emission or absorption of the gas absorber from the time points of 0 minutes, 25 minutes, 71 minutes, 96 minutes, 142 minutes, and 167 minutes is graphed. The values ​​represented by the vertical axis of the graph in FIG. 33 are the same as the values ​​represented by the vertical axis in FIG. 12. FIG. 33 shows that the obtained gel particle film achieved extremely high absorption speed, absorption amount, emission amount, and emission speed. The gel particle film after the measurement was not too swollen and was stable. In the above experiment, instead of DMAPM:BIS=95:5, a mixture of DMAPM:BIS:NIPAM=55:5:45 was used as the polymerizable compound, and a gel membrane was prepared in the same manner. Carbon dioxide absorption and desorption tests were performed to confirm the membrane state. Here, NIPAM is N-isopropylacrylamide. Figure 34 shows the graph of the emission or absorption amount of the gas absorber. As shown in Figure 34, good absorption rate, absorption amount, emission amount, and emission rate were achieved. Even when a large amount of water was added when forming the gel membrane, the membrane maintained a uniform state. In addition, even after the gas absorption and desorption test, the gel particle membrane was not too swollen and was stable. In addition, instead of the DMAPM:BIS=95:5 mixture in the above experiment, a mixture of DMAPM:BIS:NIPAM=30:5:65 was used as the polymerizable compound to prepare a gel membrane in the same manner, and carbon dioxide absorption and desorption tests were performed to confirm the membrane condition. Figure 35 shows the graph of the amount of gas absorbent that is desorbed or absorbed. As shown in Figure 35, good absorption rate, absorption amount, desorption amount, and desorption rate were achieved. Even when a large amount of water was added when forming the gel membrane, the membrane maintained a uniform state. Furthermore, even after the gas absorption and desorption test, the gel particle membrane was not too swollen and was stable. Furthermore, in the above experiment, the polymerizable compound was used in the same manner, but the solvent was changed from methanol to water, and the polymerization initiator was changed to 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone. A gel membrane was then prepared in the same manner, and a carbon dioxide absorption and desorption test was performed to confirm the membrane condition. Figure 36 shows the graph of the emission or absorption amount of the gas absorber. As shown in Figure 36, good absorption and desorption amounts were achieved, but the absorption and desorption rates were somewhat slow. Even when a large amount of water was added when forming the gel membrane, the membrane maintained a uniform state. Furthermore, even after the gas absorption and desorption test, the gel particle membrane was not too swollen and was stable.

[0098] (9) Effect of adding absorption and diffusion promoter Various low molecular weight compounds were added to the gel particle membrane as absorption and desorption promoters, and their effects on improving the amount of carbon dioxide absorbed, the absorption rate, the amount of carbon dioxide emitted, and the rate of carbon dioxide desorption were examined. A gel particle film was formed in the reactor shown in FIG. 15, and a low molecular weight compound represented by the following formula was added to the gel particle film, or amine-containing dry gel particles were placed in the reactor, and water, PMDETA containing almost no water, or an aqueous solution of PMDETA was added. Then, one cycle of carbon dioxide absorption and desorption was performed under the same conditions as those used in the measurement of FIG. 16, and the change over time in the amount of carbon dioxide absorbed and desorbed was examined. The results are shown in FIGS. 37 to 42. In FIGS. 37 to 40, "GP+H2O" represents a gel particle film that does not contain a low molecular weight compound represented by the following formula, and the others represent gel particle films to which the low molecular weight compound shown in the table was added at a concentration of 3N or 13 mass% in terms of amine concentration. In Figures 41 and 42, "GP+H2O" represents amine-containing dry gel particles to which water was added, "GP+PMDEA" represents amine-containing dry gel particles to which PMDETA containing almost no water was added, and the others represent amine-containing dry gel particles to which PMDETA aqueous solutions with amine-equivalent concentrations of 1N, 3N, and 10N were added. 37 to 42, it was confirmed that the absorption rate, absorption amount, emission amount, and emission rate were dramatically improved in the gel particle film to which an amine compound, particularly imino-bis(N,N-dimethylpropylamine) (IBDPA) or N,N',N"-pentamethyldiethylenetriamine (PMDETA), was added. In this case, if the concentration of the amine compound was too high, the amount of water relative to the amine tended to be too much, and the absorption amount tended to decrease conversely, suggesting that it is important to have an appropriate amount of water in order to improve the absorption capacity (FIGS. 41 and 42). The amount of water present is preferably 5 times or more by mole relative to the amine, more preferably 8 times or more by mole, and even more preferably 10 times or more by mole. In the gel particle film to which an amine compound was added under optimal conditions, both the absorption amount and emission amount were improved by 3 to 4 times compared to the gel particle film to which no accelerator was added (FIGS. 41 and 42).

[0099] [ka]

[0100] Various low molecular weight amines were added to the gel particle membrane as diffusion promoters, and their effect on improving the amount of carbon dioxide diffusion from the gel membrane was examined. A methanol solution (100 mg / 6 mL) of the amine-containing gel particles obtained in Synthesis Example 1 was poured into a stainless steel container, dried at 80°C, and then the stainless steel container was cooled with ice from the outside to produce a dry nanogel film. 400 μL of a 3N amine aqueous solution was uniformly dropped onto this dry nanogel film. The gel particle film thus obtained was subjected to one cycle of carbon dioxide absorption and desorption under the same conditions as those used in the measurement of FIG. 16, and the amount of carbon dioxide desorbed was examined. The results of examining the amount of desorption using various low molecular weight amines are shown in FIG. 43. As shown in FIG. 43, it was confirmed that desorption can be promoted by adding a low molecular weight amine. In addition, gel particle films were prepared in the same manner and the amount of carbon dioxide emission was examined when the concentration of the amine aqueous solution was changed to 6N and 400 μL was added, and when the concentration of the amine aqueous solution was changed to 8N and 800 μL was added. The results are shown in Figure 44. As shown in Figure 44, it was found that TMDAH had a tendency to reduce the amount of carbon dioxide emission when the amine concentration was too high, but PMDETA and IPAE were confirmed to be able to achieve high carbon dioxide emission even at high amine concentrations. In particular, IPAE achieved a significantly high carbon dioxide emission even at high amine concentrations, demonstrating a remarkably excellent effect. A high amine concentration means that the amount of water relative to the amine is small, but even under such a small amount of water condition, IPAE achieved a significantly high carbon dioxide emission. [Industrial Applicability]

[0101] According to the present invention, a gas absorber capable of efficiently absorbing and releasing acidic gases such as carbon dioxide and water vapor in response to an external temperature change is realized. Such a gas absorber can be effectively used in the process of separating and recovering acidic gases in CCS and in the process of separating acidic gases from fuel gas, and has extremely high industrial applicability. [Explanation of symbols]

[0102] 1 Acrylic plate 2 Butyl rubber gasket 3 Gas absorber 4 screws 5 Gas inlet 6 Gas outlet 11 Space section 12 Straightening plate 13 Gas inlet 14 Gas outlet 21 Heat exchanger 22, 33 Desulfurizer 23 Gas absorber 24 No. 1 Pipe 25 No. 2 Pipe 26 3rd Pipe 26a Circulation Route 26b Branching Route 31 1st heat exchanger 32 Second heat exchanger 34 First Tank 35 Second Tank 36 No. 1 Pipe 37 No. 2 Pipe 37a Main Route 37b 1st Route 37c 2nd Route 38, 39 Gel particle membrane

Claims

1. a gas inlet for introducing a gas to be treated, which contains carbon dioxide, into the gas absorbing material, which contains polymer compound particles having amino groups; A heat supply unit for applying heat to the gas absorbing material; a gas exhaust path for exhausting a portion of the gas from the gas absorbing material; and An apparatus for recovering carbon dioxide, comprising: a circulation path branched from the gas exhaust path and for introducing another part of the gas into the gas absorbing material, The heat supply unit heats the gas absorbing material by introducing into the gas absorbing material a gas in the circulation path that is heated by a heat exchanger connected to the gas introduction unit and the circulation path, The above-mentioned apparatus, wherein the gas absorbing material satisfies at least one of the following (1) and (2): (1) The water content per 1 g of solids is 0.1 mL or more. (2) The polymer compound particles having an amino group are (meth)acrylamide polymer compound particles.

2. The apparatus of claim 1 , wherein the gas absorbing material fills the (1).

3. The apparatus of claim 1 , wherein the gas absorbing material fills the (2).

4. 2. The apparatus of claim 1, wherein said gas absorbing material fills both said (1) and said (2).

Citation Information

Patent Citations

  • Adsorbent for selectively adsorbing and separating gas and its preparation

    JP1987030550A

  • Nitrogen oxide-containing gas concentrating apparatus

    JP1993057143A

  • Deodorizing device

    JP1998076133A

  • Method of removing carbon dioxide and carbon dioxide removing apparatus

    JP2001205045A

  • Flush toilet and deodorizing method of flush toilet

    JP2006097311A